Solder-carbon nanostructure composites and methods of making and using same
Solder-based composites with carbon nanostructures and metal coatings address the brittleness and reliability issues of conventional solders, enhancing thermal conductivity and mechanical reliability in SiC packages.
Patent Information
- Application Number
- JP2023536432
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-16
- Filing Date
- 2021-12-15
- Publication Date
- 2024-12-23
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional solders and their interfaces in SiC packages exhibit brittleness and reliability issues, contributing significantly to thermal resistance, which hinders the dissipation of extreme heat flux in next-generation devices.
Development of solder-based composites incorporating carbon nanostructures with metal coatings, dispersed within a polymer matrix, to enhance thermal and mechanical properties while maintaining electrical conductivity.
The composites achieve improved thermal conductivity, reduced thermal resistance, and enhanced mechanical reliability, effectively addressing the brittleness and reliability issues of conventional solders in SiC packages.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of and priority to U.S. Provisional Application No. 63 / 126,432, filed December 16, 2020, which is incorporated by reference herein in its entirety.
[0002] FIELD OF THEINVENTION FIELD OF THEINVENTION The present invention is in the field of carbon nanostructures, including solder composites, and methods of making and using same. [Background technology]
[0003] 2. Background of the Invention To dissipate the extreme heat fluxes expected in next-generation SiC devices, a 0.1 cm 2 -K / W total package resistance is required. However, if the material is less than 0.1cm 2 -The thermal resistance of the materials found in such SiC packages must be addressed, which accounts for almost 80% of the K / W target. For example, the solder and its interfaces account for at least 30% of the resistance count.
[0004] Thus, there is a need to address the brittleness and reliability issues of conventional solders and interfaces formed therefrom while maintaining metal-like thermal resistance.
[0005] Therefore, a need exists to provide improved solder-based composites and methods for making the same.
[0006] SUMMARY OF THE PRESENT EMBODIMENT It is therefore an object of the present invention to provide a solder-based composite.
[0007] A further object of the present invention is to maintain / preserve the electrical, thermal and mechanical properties of the solder-based composite.
[0008] It is a further object of the present invention to provide an easy and scalable method for manufacturing such solder-carbon nanotube composites.
[0009] It is a further object of the present invention to provide methods of using such solder-carbon nanotube composites. Summary of the Invention
[0010] Summary of the Invention Solder-Carbon Nanostructures body Described herein are composites and methods of making and using the same. body The composite is dispersed in the solder material. A plurality of carbon nanostructures thereon. Metal coating included fruit, The carbon nanostructures include a plurality of carbon nanostructures having lengths in the range of 1 to 1000 microns, the plurality of carbon nanostructures including defects thereon due to exposure to plasma treatment, acid bath treatment, or due to a growth process of the plurality of carbon nanostructures, and / or the plurality of carbon nanostructures including functional groups thereon due to a polymer encapsulating the plurality of carbon nanostructures.
[0011] Solder-carbon nanostructures as described herein body In one method of forming the complex, the method comprises: (1) forming or providing a carbon nanostructure array; (2) optionally encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which may be a polymer-based material; (3) optionally exposing the optionally encapsulated carbon nanostructure array to a treatment that creates defect sites on the carbon nanostructures; (4) As necessary, The above removing the encapsulant; (5) Formed during step (3) The array Carbon Nanostructures on the body depositing or forming a metal-based coating on the substrate; (6) Molten solder material The array Carbon Nanostructures On the body The infiltration process; (7) The solder-carbon nanostructure, in which the carbon nanostructure is dispersed within the composite. body To form a complex, the allowing the mixture to cool; and (8) Optionally, the solder-carbon nanostructure body and c) encapsulating the composite in a polymer or blend of polymers.
[0012] Solder-carbon nanostructures as described herein body In a second method of forming a complex, the method includes: (1) forming or providing a carbon nanostructure array; (2) optionally encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which may be a polymer-based material; (3) optionally exposing the optionally encapsulated carbon nanostructure array to a treatment that creates defect sites on the carbon nanostructures; (4) As necessary, The above removing the encapsulant; (5) Formed during step (3) The array Carbon Nanostructures on the body depositing or forming a metal-based coating on the substrate; (6) Molten solder material The array Carbon Nanostructures On the body a penetrating step, wherein the solder material remains in a liquid state; (7) Optionally, the solder-carbon nanostructure body and c) encapsulating the composite in a polymer or blend of polymers.
[0013] Solder-carbon nanostructures as described herein body In yet a third exemplary method of forming a complex, the method includes: (1) forming or providing a carbon nanostructure array; (2) encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which is a polymer-based material; (3) depositing or forming a metal-based coating on the encapsulated carbon nanostructures of the array; (4) infiltrating the encapsulated carbon nanostructures of the array with a molten solder material; (5) The solder-carbon nanostructure, in which the carbon nanostructure is dispersed within the composite. body To form a complex, the allowing the mixture to cool; and (6) Optionally, encapsulating the solder-carbon nanostructures in a polymer or polymer blend.
[0014] Solder-carbon nanostructures as described herein body The composites can be used in a variety of applications, including thermal applications. For example, the solder-carbon nanostructures described body The composite may be disposed or secured between a heat source and a heat sink or heat spreader, such as between an integrated circuit package and a heat exchanger, to improve the transfer of heat from the heat source to the heat sink or spreader.
[0015] In certain embodiments, the solder carbon nanostructures including the composites described herein can be used as thermal interface materials (TIMs) in personal computers, server computers, memory modules, graphics chips, radar and radio frequency (RF) devices, disk drives, displays including light emitting diode (LED) displays, lighting systems, automotive control units, power electronics, solar cells, batteries, communication devices such as mobile phones, thermoelectric generators, and imaging devices including MRI. [Brief description of the drawings]
[0016] [Figure 1]FIG. 1 shows a schematic diagram of a method for fabricating a solder-carbon nanotube composite that involves functionalization of vertically aligned carbon nanotube arrays (VACNTs), followed by conformal coating with a high surface energy coating such as a metal coating, and application of molten solder to the coated VACNT arrays to form a CNT solder composite.
[0017] [Diagram 2] FIG. 2 shows graphs of Raman spectra showing the peak shifts of (a) as-grown CNT arrays w amorphous carbon and samples D and G after (b) 1, (c) 2, and (d) 3 min of oxygen plasma treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Detailed Description of the Invention Solder-Carbon Nanostructures body Described herein are conjugates and methods of making and using them.
[0019] I. Definition As used herein, "substrate" or "support" refers to the material on which nanotubes are grown. A variety of materials can function as the support. Generally, the support is inert, meaning that it does not chemically participate in the formation of nanotubes on the multilayer substrate. In some embodiments, the support is at least partially formed from a metal, including, but not limited to, aluminum, cobalt, chromium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, copper, or combinations thereof, and / or one or more metal oxides, such as the oxides of the metals listed above.
[0020] As used herein, "conformal" or "conformally coated" means covering the surface topography of an object such that it is completely or effectively covered and the covered surface is free or substantially free of pinholes or other defects that expose the underlying material of the object.
[0021] As used herein, a "carbon nanotube array" or "CNT array" or "CNT forest" refers to a plurality of carbon nanotubes aligned vertically on a surface of a material, such as a substrate or support. Carbon nanotubes are said to be "vertically aligned" when they are substantially perpendicular to the surface on which they are supported or attached. Nanotubes are said to be substantially vertical when they are oriented within an average of 30, 25, 20, 15, 10, or 5 degrees of the surface normal.
[0022] As used herein, "polymer coating" generally refers to a polymer or molecule that is bonded to the CNTs via van der Waals bonding, π-π stacking, mechanical wrapping and / or covalent bonds, and to the metal, metal oxide, or semiconductor material surface via van der Waals bonding, π-π stacking, and / or covalent bonds.
[0023] As used herein, "thermal interface material" (TIM) refers to a material or combination of materials that provides high thermal conductance and mechanical compliance between a heat source and a heat sink or spreader to effectively transfer heat away from the heat source.
[0024] As used herein, "coefficient of thermal expansion" refers to a measure of the change in size, such as volume, per degree of change in temperature at constant pressure.
[0025] "Electrical conductivity" or "specific conductivity" as used herein refers to the degree to which a material can conduct electric current, as calculated as the ratio of the current density in the material to the electric field that drives the current flow. It is the reciprocal of electrical resistivity. Electrical conductivity is typically reported in SI units of siemens per meter (S / m).
[0026] As used herein, "thermal contact resistance" refers to when two surfaces are in thermal contact and there is a resistance to heat transfer between the surfaces.
[0027] "Thermal conductivity" as used herein refers to the transport of energy in the form of heat through a mass as a result of a temperature gradient and is determined as the heat energy transferred per unit time and per unit surface area divided by the temperature gradient. Thermal conductivity is typically expressed in Wm -1 K -1 It is expressed in units of.
[0028] "Tensile modulus," as used herein, alternatively known as Young's modulus or elastic modulus, refers to a measure of the stiffness of a material and is a measure of the ratio of the stress along an axis to the strain along the same axis. Tensile modulus can be used to describe the elastic properties of a material or object when stretched or compressed.
[0029] Numerical ranges disclosed in this application include, but are not limited to, temperature ranges, pressure ranges, weight ranges, ratio ranges, integer ranges, conductance and resistance ranges, time ranges, and thickness ranges. Any type of disclosed range separately discloses each possible number that such range can reasonably encompass, as well as any subranges and combinations of subranges encompassed therein. For example, the disclosure of a thickness range is intended to separately disclose all possible thickness values that such range can encompass, consistent with the disclosure herein.
[0030] Use of the term "about" is intended to describe values above or below the stated value that the term "about" modifies by a range of about + / - 10%. In other examples, values may range above or below the stated value by a range of about ±5%. When the term "about" is used before a range of numbers (i.e., about 1-5) or before a series of numbers (i.e., about 1, 2, 3, 4, etc.), it is intended to modify both ends of the range of the series of numbers or each of the series of numbers, unless otherwise specified.
[0031] II. Solder-Carbon Nanostructures body Complex A. Metallic Substrates / Supports for Vertically Aligned Carbon Nanostructures A variety of materials can serve as supports or substrates for the vertically aligned array of tubular shaped nanocarbon (i.e., carbon nanotube) materials. In some embodiments, the substrate or support is at least partially formed from a metal, such as, but not limited to, aluminum, cobalt, chromium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, copper, or combinations thereof, and / or one or more metal oxides, such as oxides of the metals listed above. In other embodiments, the material can be, but is not limited to, ceramics and silicon or silicon compounds, such as silicon dioxide. In certain other embodiments, the substrate or support is a metal foil, such as, but not limited to, aluminum foil or copper foil.
[0032] In some embodiments, the surface of the support may be treated to increase adhesion of the formed carbon nanostructures by including an appropriate adhesion layer or surface treatment, which may include the use of plasma-assisted or chemical-based surface cleaning. Other treatments may include the deposition of metal or metal oxide coatings or particles onto the support.
[0033] The substrate or support and conditions under which vertically aligned arrays of carbon nanostructures, such as carbon nanotubes (CNTs), are formed may be selected such that the support is not prone to react with the catalyst, process gases, and / or residual gases through reactions such as oxidation, silicidation, alloying, and / or carbide formation. For example, C, O, H, and N are elements that constitute most CNT CVD processes and contaminant gases. Reaction conditions, such as temperature, may be selected to minimize adverse reactions of the support.
[0034] B. Vertically aligned carbon nanostructures forming an array In certain embodiments, the carbon nanostructures form tubular structures (i.e., carbon nanotubes) that form vertically aligned forests or arrays. In certain embodiments, the vertically aligned carbon nanostructures are single-walled, double-walled, triple-walled, or higher multi-walled carbon nanotubes having diameters in the range of 10-40 nm, more preferably 15-30 nm, and most preferably about 20 nm or less. The length of such other carbon nanostructures may range from 0.01 to 5,000 microns, preferably 0.1 to 2500 microns, preferably 0.1 to 2000 microns, and more preferably 0.1 to 1000 microns.
[0035] In other embodiments, the carbon nanostructures can form, without limitation, fibers, wires, horns, cones, or other tubular structures having a high aspect ratio (i.e., greater than 1.) The length of such other carbon nanostructures can range from 0.01 to 5,000 microns, preferably 0.1 to 2500 microns, preferably 0.1 to 2000 microns, and more preferably 0.1 to 1000 microns.
[0036] In a preferred embodiment, the vertically aligned carbon nanostructure array comprises a plurality of vertically aligned carbon nanotubes on a surface of a metal or metal-containing support or substrate.
[0037] In certain embodiments, the carbon nanostructure arrays are grown on the described substrate by chemical vapor deposition. Other methods of growing vertically aligned carbon nanostructure arrays are known in the art. Generally, the nanotubes are present in sufficient density such that the nanotubes are self-supporting and oriented substantially perpendicular to the surface of the substrate or support. In some embodiments, the nanotubes forming the array are oriented within an average of 30, 25, 20, 15, 10, or 5 degrees of the surface normal of a line drawn perpendicular to the surface of the substrate or support. Preferably, the nanotubes are spaced an optimal distance from each other and are of uniform height.
[0038] In a particular embodiment, the carbon nanostructures are about 1×10 7 ~1×10 11 Nanotubes / mm 2 , more preferably about 1×10 8 ~1×10 10 Nanotubes / mm 2 , and most preferably about 1×10 9 ~1×10 10 Nanotubes / mm 2 The carbon nanotubes have a density on the support or substrate surface in the range of 0.1 to 1.0 μm.
[0039] The carbon nanostructure arrays grown on the substrate contain defect sites thereon. For example, when the carbon nanostructures are carbon nanotubes, the carbon nanotubes can contain defects such as vacancies, interstitials, and most commonly bond rotations and non-hexagonal rings (e.g., 5-C pentagonal defects). The solder-carbon nanostructures described body For purposes of forming a composite, the carbon nanostructure array grown on the substrate can be further exposed to conditions that generate more defect sites on the carbon nanostructures, if desired. For example, as described in the fabrication methods section below, the carbon nanostructure array grown on the substrate can be exposed to a plasma-based treatment (i.e., oxygen plasma) and / or an acid bath treatment (i.e., nitric acid bath) to produce a higher number of defects compared to arrays that have not been treated with the plasma and / or acid bath treatment. Array Carbon Nanostructures on the body The introduction of defect sites can facilitate and improve the ability to deposit metals and mixtures thereof to form metal-based coatings, as described in Section C below. However, as described herein, plasma and / or acid treatments can damage or destroy carbon nanostructure arrays grown on a substrate, and it is recommended that the carbon nanostructure arrays grown on a substrate be pretreated prior to exposing the arrays to such treatments. Array Carbon Nanostructures Body It must be encapsulated in a suitable encapsulant, such as a polymer coating.
[0040] Thus, after formation of the carbon nanostructure array grown on the substrate, an encapsulant is applied to form a protective layer on the carbon nanostructure array (i.e., carbon nanotubes). The encapsulant is a polymer-based coating formed from one or more polymers selected from, but not limited to, conjugated polymers, non-conjugated polymers, and / or aromatic polymers. In some examples, the polymer is a thermoplastic elastomer such as polyester-based polyurethane or styrene-ethylene-butylene-styrene, polyimide, polyamide, or blends thereof. The polymer-based coating can be spray-coated or the array of vertically aligned carbon nanostructures can be immersed in a polymer solution. In some other embodiments, the polymer-based coating comprises one or more oligomeric materials, polymeric materials, or combinations thereof. In certain embodiments, the polymer may be selected from poly(3,4-3 ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS), poly(3,4-3 ethylenedioxythiophene) (PEDOT), polythiophene (including alkyl-substituted polythiophene), polystyrene, silicone, polysiloxane, polypyrrole, polyacetylene, polyaniline, polyfluorene, polyphenylene, polypyrene, polyazulene, polynaphthalene, polycarbazole, polyindole, polyazepine, poly(3,4-ethylenedioxythiophene), poly(p-phenylsulfide), and poly(p-phenylenevinylene), polyacetylene, polydiacetylene, and blends thereof. In certain cases, the polymer may be selected from silicone or polysiloxane. The polymer classes listed above include substituted polymers in which the polymer backbone is substituted with one or more functional groups, such as alkyl groups. The polymer can have any suitable weight average molecular weight or polydispersity. In some examples, the weight average molecular weight can be in the range of 2,000 Da to 750,000 Da and subranges disclosed therein.
[0041] The encapsulant can provide a protective barrier for the carbon nanostructure array (i.e., carbon nanotubes) when exposed to plasma and / or acid bath treatments, allowing for the introduction of defect sites into the carbon nanostructure array (i.e., carbon nanotubes) by preventing destruction of the carbon nanostructures (i.e., carbon nanotubes), such as by oxidation, and / or delamination of the carbon nanostructures (i.e., carbon nanotubes) from the substrate on which they were grown. Additionally, the polymer-based coating forms a semi-porous film over the carbon nanostructure array (i.e., carbon nanotubes), with the pores allowing access to the underlying structure during plasma and / or acid bath treatments. This allows for the introduction of defect sites in a controlled manner that can prevent excessive damage to the carbon nanostructure array (i.e., carbon nanotubes). As described in more detail below, the encapsulant (i.e., protective layer) can be subsequently removed by application of a solvent after the plasma and / or acid bath treatments have introduced additional defect sites. Alternatively, in some instances, a treatment such as oxygen plasma can etch away the encapsulant (i.e., protective layer) during exposure, with the encapsulant (i.e., protective layer) acting as a sacrificial layer.
[0042] In some examples, the polymer encapsulant (such as in the case of a conjugated polymer) may itself be used to act as a non-covalent functionalization mechanism for the sidewalls of the carbon nanostructures (i.e., carbon nanotubes). Aromatic molecules such as pyrene, porphyrin, polyacetylene, polythiophene, polyfluorene, polypyrrole, and poly(phenylenevinylene) and their derivatives on the polymer can interact with the sidewalls of the carbon nanotubes through π-π stacking and van der Waals interactions between the conjugated polymer chains containing aromatic rings and the surface of the carbon nanotubes. The polymer may have any suitable weight average molecular weight or polydispersity. In some examples, the weight average The average molecular weight can range from 2,000 Da to 750,000 Da and subranges disclosed therein. These polymers can wrap around the nanotubes and can serve as functionalization sites through functional groups incorporated into the polymer itself, through nanoparticle dispersions incorporated into the polymer matrix, or by modifying the surface energy mismatch between the carbon nanostructure and a subsequent metal-based coating deposited thereon. Exemplary functional groups on the polymer include, for example, phosphines, phosphonates, phosphonic acids, diphosphenes, sulfonates, thiols, amines, amides, carboxylic acids, carboxylates, haloalkanes (C containing halogen substituents), and the like. 1 -C 10 In such cases described in this paragraph, the encapsulant-encapsulated carbon nanostructures of the array do not need to be treated to create additional defects and may be coated with a metal coating as detailed herein.
[0043] Array Carbon Nanostructures BodyAfter treatment (i.e., plasma-based or acid bath) to introduce additional defects, these can be referred to as defect-containing carbon nanostructures (i.e., carbon nanotubes) of the array. "Defect-containing" carbon nanostructures (i.e., carbon nanotubes) refer to carbon nanostructures (i.e., carbon nanotubes) that contain more / added defects compared to the carbon nanostructures (i.e., carbon nanotubes) prior to treatment. In some examples, the defect-containing carbon nanostructures (i.e., carbon nanotubes) of the array contain about 1%-50%, 1%-40%, 1%-30%, 1%-25%, 1%-20%, 1%-15%, 1%-10%, or 1%-5% more defects relative to the amount of defects in the as-formed and untreated carbon nanostructures (i.e., carbon nanotubes) of the array. Methods for determining the amount of defects in carbon nanostructures include, for example, Raman spectroscopy, where an increase in the G peak (~1350 cm-1) peak relative to the D (~1575 cm-1) peak can be correlated with an increase in overall amorphous carbon and an increase in the number of defect sites in the array. In some instances, exposure to a treatment (such as plasma-based or acid bath treatment) may initially increase the D peak as less favorable defects or adsorbates or amorphous carbon etc. are removed from the array before increasing the G band defects after the native CNTs are fully exposed. Figure 2 shows measurements of the Raman shift of samples after 1, 2, and 3 minutes of oxygen plasma treatment.
[0044] C. Metal-based coatings on vertically aligned carbon nanostructures forming arrays After the additional defect sites are formed on the carbon nanostructure array (i.e., carbon nanotubes), a metal-based coating is optionally applied to improve the wetting and dispersibility of the carbon nanostructures (i.e., carbon nanotubes) in the solder material. Generally, the metal-based coating can be applied using any technique known in the art.
[0045] As discussed above, the introduction of additional defect sites allows for the facile deposition or formation of metal-based coatings on the carbon nanostructure arrays (i.e., carbon nanotubes). The metal-based coating can be a conformal coating, such as, but not limited to, a nanoscale coating formed from a metal, a metal alloy, and / or a metal oxide. In some embodiments, the metal can be aluminum, bismuth, cobalt, chromium, zinc, gallium, tantalum, platinum, gold, nickel, iron, tin, lead, silver, tungsten, titanium, indium, copper, or combinations or alloys thereof, and / or one or more metal oxides, such as, but not limited to, oxides of the metals listed above. In some examples, the conformal coating is not a continuous film, but a dense decoration of individual nanoparticles along the length of the carbon nanotube from tip to base. In some other examples, the metal-based coating need not be a conformal coating, but instead may be present only at or near the tip of the array. This type of coating can be used, for example, to form a solder carbon nanostructure. body The composite is only present in a thin film near the tip of the array, with the remaining length of the array having no solder component, and instead being either only or substantially only carbon nanotubes, or a carbon nanotube-polymer composite with the polymers listed above as encapsulants may be used to achieve this.
[0046] In some specific examples, the metal-based coating matches the solder material composition or Array Carbon Nanostructures Body The metal is selected to match at least one or more metals present in the solder material being dispersed. For example, most solders contain tin as a major component. Any suitable solder known in the art can be used. Thus, the metal-based coating can be applied to the solder-carbon nanostructure. bodyTo form a composite, it can be selected to include tin and optionally one or more additional metals that are commonly used in solder alloys to improve the wetting and dispersibility of the carbon nanostructures in a particular solder material.
[0047] In certain embodiments, the carbon nanostructures (i.e., carbon nanotubes) are conformally coated on the sidewalls of the CNTs and, optionally, on the tips of the carbon nanostructures (i.e., carbon nanotubes), or vice versa. In certain other embodiments, the carbon nanostructures (i.e., carbon nanotubes) are conformally coated on both the sidewalls of the carbon nanostructures (i.e., carbon nanotubes) and the tips of the carbon nanostructures (i.e., carbon nanotubes). As described in the manufacturing methods section below, to facilitate the formation of metal-based coatings on the carbon nanostructures, it is useful to introduce defect sites on the carbon nanostructures, such as by plasma and / or acid treatment. The introduction of defect sites by such treatments provides sites for metal deposition for the formation of metal-based coatings as described herein.
[0048] In certain embodiments, at least about 100%, 99%, 98%, 97%, 96%, 95%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, or 10% of the surface of the carbon nanostructure (i.e., carbon nanotube) is coated with the metal-based coating. In certain non-limiting embodiments, the thickness of the metal-based coating, such as the nanoscale conformal coating, can be in the range of about 0.1 to 50,000 nanometers, 500 to 50,000 nanometers, 1 to 10,000 nanometers, 5 to 5,000 nanometers, 5 to 1,000 nanometers, 5 to 500 nanometers, 5 to 250 nanometers, 0.1 to 1,000 nanometers, 1 to 500 nanometers, 5 to 250 nanometers, more preferably 5 to 100 nanometers, 5 to 50 nanometers, or 5 to 25 nanometers.
[0049] In certain embodiments, the percentage of metal deposited on the carbon nanostructures (i.e., carbon nanotubes) can be defined as a weight percentage determined, for example, using energy dispersive spectroscopy (EDS). For example, the metal weight percentage in the metal coated array can range from about 5-40% or 5-35% by weight. In some examples, the metal coated array exhibits a metal to carbon weight ratio (e.g., as determined by EDS) in the range of about 0.1-1.5 or 0.1-1, while in other examples, the ratio is about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, or 1.2.
[0050] i. Methods for depositing metal-based coatings In certain embodiments, the solder-carbon nanostructure body Prior to forming the composite, a metal-based coating can be deposited on the plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming the array to obtain a conformal metal coating on the carbon nanostructures (i.e., carbon nanotubes) as desired.
[0051] In some embodiments, the metals, metal alloys, metal oxides, or combinations of the above metals. 1 of 1 One or more coatings may be applied using atomic layer deposition (ALD). In some other embodiments, the coating may be a metal, a metal alloy, a metal oxide, or a combination thereof. 1 of 1 One or more coatings can be deposited, such as via chemical vapor deposition (CVD), on the plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming the array. In yet other embodiments, a metal, metal alloy, metal oxide, or combination thereof can be deposited on the plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming the array. 1 of 1One or more coatings can be deposited, such as by sputtering, onto a plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming an array. ALD can be used, for example, to deposit desired metal-based coatings with high conformality and precise control of thickness. Deposition is controlled at the atomic level by self-limiting surface reactions. This results in uniform and conformal deposition on the high aspect ratio porous structures due to the self-passivation of the surface chemistry. Once a reaction is completed at one surface site, the reactants continue down the high aspect ratio pores to reach unreacted surface sites.
[0052] Methods for ALD, CVD, and sputter coating metal-based coatings, as well as the reaction conditions and equipment required to achieve such metal-based coatings, are well known in the art. Selection of appropriate metal precursors to form the desired metal-based coatings includes, but is not limited to, aluminum, bismuth, cobalt, chromium, zinc, gallium, tantalum, platinum, gold, nickel, iron, tin, lead, silver, tungsten, titanium, indium, copper, and alloys / combinations are also known. In one example, a metal-based coating including tin doped with chromium can be sputter coated onto carbon nanostructures. This can be matched to the composition of commercially available solders, for example, C-Solder sold by Goodfellow USA contains 90-100% tin, 0.01-1% copper, 3-5% silver, and 2-6% chromium.
[0053] In some examples, the metal-based coating can be a multi-layer coating having, for example, a carbon nanostructure adhesion layer, a solder adhesion layer, and a low-reactivity layer. Examples of the carbon nanostructure (i.e., carbon nanotube) adhesion layer can be made of metals including Ti or Cr. The solder adhesion layer can be made of metals including tungsten, copper, aluminum, nickel, tin, indium, lead, bismuth, or alloys / combinations thereof. Low-reactivity layer materials can include platinum, gold, and silver. In some examples, a layer can perform more than one function, such that only one or two of the above-mentioned layers are present.
[0054] In a specific, non-limiting example, the surface of a plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming an array is coated by ALD with a platinum coating. The platinum coating may have any suitable thickness, but in some examples may be a 20 nm thick coating. For example, platinum is a low-reactivity metal that is believed to allow flux-free infiltration of the array with molten solder material, and thus the solder-carbon nanostructures. body There are also a wide variety of platinum precursors readily available for use in ALD processes.
[0055] A common limitation in metal deposition using ALD is the availability of a reducing agent that can adsorb and exothermically react with surface-adsorbed metal precursors, allowing ALD to proceed at temperatures below 350 °C. Of all ALD metal deposition processes, ALD tungsten (W) is prepared using tungsten hexafluoride (WF 6 ) and silane (SiH 4 ) or disilane (Si 2 H 6 ) as a reactant. In some instances, the advantage of using W as the metallic coating is that due to its high atomic number, the resulting composite is effective at preventing the penetration of radiation. This is particularly beneficial for applications such as the protection of electronic equipment that must operate in environments such as space, where cosmic radiation bombardment is common.
[0056] In some examples, a nanoscale alumina coating is deposited prior to the metal deposition of the metal-based coating, which can serve to functionalize and improve the conformal deposition and adhesion of the successively coated metal-based coating on the array.
[0057] In certain other non-limiting embodiments, the metal-based coating is formed by a wet coating method. In such a method, the surface of a plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming an array is infiltrated with a liquid phase containing a metal precursor capable of decomposing into elemental metal, thereby forming and depositing the metal on the surface of the carbon nanostructures (i.e., carbon nanotubes), particularly at existing defect sites that facilitate the formation / deposition of the metal from the precursor. The decomposition of the metal precursor and the formation of the metal-based coating therefrom is typically accomplished by immersing the array-forming carbon nanostructures (i.e., carbon nanotubes) in a suitable solvent containing the metal precursor dissolved therein, and applying heat in an inert environment to pyrolyze the metal precursor and form the coating. Exemplary precursors include metal isopropoxides, metal hydrides (such as, but not limited to, titanium hydride, AlH 3 {O(C 4 H 9 ) 2 , AlH 3 {N(CH 3 ) 3}), galistan, and metal salts. Metal salts can include, but are not limited to, silver nitrate, silver neodecanoate, silver oxalate, silver acetate, silver tartrate, silver hexafluoroacetylacetonate cyclooctadiene, copper acetate, copper formate tetrahydrate, copper formate, copper glycolate, copper lactate, copper oleate, copper hydroxide, nickel sulfate, and nickel acetate. Details of the wet coating process for forming the metal-based coating are described below in the manufacturing method.
[0058] Without wishing to be bound by any particular theory, it is believed that modification of carbon nanostructures (i.e., carbon nanotubes) by forming defect sites thereon facilitates the deposition of one or more metal-based coatings, thereby providing the solder-carbon nanostructures described herein. body This can allow for better / improved wetting of the solder material to the carbon nanostructure arrays (ie, carbon nanotubes) to form a composite.
[0059] In certain embodiments, the one or more metal-based coatings applied to the CNTs that modify the wetting properties also modify and improve the dispersibility of the carbon nanostructure arrays (i.e., carbon nanotubes) when placed in contact with molten solder. The improved wetting properties and dispersibility are achieved by allowing the carbon nanostructure arrays (i.e., carbon nanotubes) to disperse more readily in the formed solder-carbon nanostructures. body The term "uniformly dispersed" as used herein refers to the amount of the metal-carbon nanostructure that can be obtained by dispersing the metal-carbon nanostructure uniformly within the composite, up to 1000 microns or more. body It refers to carbon nanostructures dispersed within the resulting metal-based composite having a high or substantially high degree of uniformity and homogeneity throughout the composite. The uniformity and homogeneity of the carbon nanostructures dispersed within the composite can be determined by techniques such as, but not limited to, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and neutron scattering.
[0060] In certain embodiments, the improved wettability results in improved dispersibility of the array of metal coated carbon nanostructures (i.e., carbon nanotubes) when placed in a solder melt. In some non-limiting embodiments, the array of metal coated carbon nanostructures (i.e., carbon nanotubes) are added / mixed into a suitable molten solder material to form a solder-carbon nanotube composite. In some non-limiting embodiments, the array of metal coated carbon nanostructures (i.e., carbon nanotubes) are immersed in a suitable molten solder material, and the temperature of the melt is lower than the melting temperature of the support / substrate on which the carbon nanostructure (i.e., carbon nanotube) array is formed in order to maintain the structure of the substrate / support and the vertical orientation of the CNT array.
[0061] D. Solder-Carbon Nanostructures body Complex Solder-carbon nanostructures as described herein body The composite includes a plurality of carbon nanostructures (i.e., carbon nanotubes) dispersed therein. In certain embodiments, the solder of the composite is a metal or metal alloy selected from, but not limited to, aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof. In some cases, the solder material of the composite is gold-tin solder, tin-silver-copper solder, tin-copper solder, tin-lead solder, tin-chromium solder, gallium solder, gallium-indium-tin solder, or indium solder. In some cases, the solder is a commercially available solder material known in the art, such as lead-free solder. The solder is typically formed primarily of tin, optionally alloyed with other metals. The composition of the solder material can be selected to have any suitable melting temperature or melting temperature range from about -19 to 300°C. The composition of the solder material can be selected to have any suitable tensile strength, typically ranging from about 0.15 to 40 kilopounds per square inch.
[0062] In certain cases, the solder material can be selected to remain in its liquid state during operation, for example, gallium-indium-tin solder. In these examples, the disclosed solder-carbon nanostructures body The composite is a solder-carbon nanostructure. body The mechanical strength of the carbon nanostructures is relied upon to provide structural integrity to the composite. In its liquid state, the solder remains substantially inside the carbon nanostructure array due to its affinity with the metal coating applied to the carbon nanostructures. In some cases, when the solder remains in a liquid state, the solder-carbon nanostructure array body The composite exists at an interface (such as between two plates) and an external force, such as a clamping force, can be used to maintain contact at the interface using bolts, nuts, clips, pins, rivets, adhesives or epoxies to cause the solder components to be in their liquid state and hold the composite together.
[0063] In some embodiments, the plurality of carbon nanostructures (i.e., carbon nanotubes) dispersed in the solder of the composite are non-bundled structures. In some other embodiments, the plurality of nanocarbon structures dispersed in the solder of the composite are substantially non-bundled structures exhibiting some degree of bundling, typically less than 15%, less than 10%, less than 5%, or less than 1% bundling. As used herein, "bundling" typically refers to a grouping of at least two or more carbon nanostructures. In some embodiments, the plurality of carbon nanostructures are uniformly dispersed within the formed solder-carbon composite, and the resulting metal-carbon nanostructure is body They exhibit a high or substantially high degree of uniformity and homogeneity throughout the composite. Methods for characterizing the uniformity of the dispersed carbon nanostructures in the solder-based composite include, but are not limited to, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS).
[0064] In certain embodiments, the filling ratio, or percentage by weight, of the dispersed carbon nanostructures in the solder-based composite ranges from about 0.1-90%, 1-80%, 1-70%, 1-60%, 1-50%, 1-40%, 1-30%, 1-20%, and 1-10%.
[0065] In some embodiments, at least one carbon nanostructure (i.e., carbon nanotube) dispersed in the solder of the composite has a length in the range of 0.01 to 5,000 microns, preferably 0.1 to 2500 microns, preferably 0.1 to 2000 microns, more preferably 0.1 to 1000 microns. In some embodiments, the length of at least one of the carbon nanostructures (i.e., carbon nanotube) forming the plurality of carbon nanostructures is in the range of 100 to 1000 microns.
[0066] In certain embodiments, the metal support or substrate on which the carbon nanostructure arrays (i.e., carbon nanotubes) are formed is the same metal as the metal of the metal solder of the formed composite, while in certain other embodiments, the metal support or substrate is a different metal.
[0067] In some embodiments, the solder-based composite includes carbon nanostructures dispersed therein, such as carbon nanotubes, aligned along the plane of the formed metal-carbon composite. In certain embodiments, the carbon nanotubes can be controllably aligned along an in-plane direction. In certain other embodiments, the carbon nanotubes can be controllably aligned along a cross-plane direction. In certain other embodiments, the carbon nanotubes can be controllably aligned along a mid-plane direction.
[0068] In certain embodiments, the solder-carbon nanostructures described herein body The composite has a thermal or electrical conductivity at least equal to the thermal or electrical conductivity of the solder material without the carbon nanostructures dispersed therein.
[0069] In certain other embodiments, the solder-carbon nanostructures described herein body The composite has a thermal or electrical conductivity at least 50%, 60%, 70%, 80%, 90%, 95%, 96%, 97%, 98%, or 99% equal to the thermal or electrical conductivity of the solder without the carbon nanostructures dispersed therein. The percentages listed refer to a comparison of the thermal or electrical conductivity of the composite to the initial thermal or electrical conductivity of the solder material.
[0070] In certain embodiments, the solder-carbon nanostructures described herein body The composite has an electrical conductivity that is at least 100% or greater than the initial solder material without any dispersed carbon nanostructures therein. In certain embodiments, the electrical conductivity is up to about 105%, 110%, 115%, 120%, 125%, 130%, 135%, 140%, 145%, 150%, or more for the solder-carbon nanostructure containing composites described herein relative to the initial solder material. In certain other embodiments, the solder-carbon nanostructure containing composites described herein have an electrical conductivity that is at least 100% or greater than the initial solder material. body The specific conductivity of the composite is about 150%, 175%, 200% or more higher than the specific conductivity of the initial solder without the carbon nanostructures dispersed therein.
[0071] In certain embodiments, the solder-carbon nanostructures described herein body The composite has a thermal conductivity that is at least 100% greater than the thermal conductivity of the solder material that does not have carbon nanostructures dispersed therein, hi certain embodiments, the thermal conductivity of the composite increases by more than about 20%, 30%, 40%, 50%, 60%, 70%, or 80% in the in-plane or cross-plane directions relative to the thermal conductivity of a comparable initial solder material.
[0072] In some embodiments, the solder-carbon nanostructures described herein body The composite may be about 5, 4, 3, 2, 1, 1.5, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.05, or 0.01 cm 2It has a thermal resistance of less than K / W.
[0073] In some embodiments, the solder-carbon nanostructures described herein body The composite has a thermal conductivity in the direction of carbon nanostructure (i.e., carbon nanotube) alignment in the range of about 1-2500 W / m·K, 1-2000 W / m·K, 1-1500 W / m·K, 1-1000 W / m·K, 1-500 W / m·K, 5-500 W / m·K, 5-400 W / m·K, 5-300 W / m·K, 5-200 W / m·K, 5-150 W / m·K, or 5-100 W / m·K. In some examples, the range is about 4-65 W / m·K.
[0074] In certain embodiments, the solder-carbon nanostructures described herein body The composite has a coefficient of thermal expansion that is about 50, 40, 30, 20, or 10% of the value of the comparable initial solder material. body The nature of the composite performance is such that stresses (e.g., thermal expansion, shock, and vibration, etc.) from one side of the composite interface are not transferred or are transferred at a lesser magnitude to the other side of the composite interface because the carbon nanostructure array carries the stress instead of the solder material. As used herein, "lesser magnitude" refers to a transfer of less than about 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, or 10% of the original magnitude of the stress experienced on the other side of the interface.
[0075] In certain embodiments, the solder-carbon nanostructure body The composites experience lower die shear strength or reduced thermal performance after exposure to thermal cycling than similar solder-only joints (i.e., joints containing only solder) subjected to the same fatigue failure mechanisms. In some instances, joints joined only with solder or sintered silver and experiencing fatigue failure when subjected to thermal cycling or high temperatures are those that contain solder carbon nanostructures as described herein. body The composite is used to maintain mechanical and thermal contact when bonded.
[0076] In certain other embodiments, the solder-carbon nanostructures described herein body The composite has mechanical properties that are different from the initial solder that does not have the carbon nanostructures dispersed therein. body The composites exhibit a reduction in failure modes common to conventional solders, such as brittle fracture, thermal expansion cracking, and whiskers. In some embodiments, the solder-carbon nanostructure body The tensile modulus of the composite is in the range of about 0.1 to about 10 GPa. In some embodiments, the solder-carbon nanostructure body The tensile modulus of the composite is about 30, 40, 50, 60, 70, 80, 90, or 100% of the value of the initial solder.
[0077] III. Solder-Carbon Nanostructures body Method for preparing the complex Solder-carbon nanostructures as described herein body In the method of forming a complex, the first method comprises: (1) forming or providing a carbon nanostructure array; (2) optionally encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which may be a polymer-based material; (3) optionally exposing the optionally encapsulated carbon nanostructure array to a treatment that creates defect sites on the carbon nanostructures; (4) As necessary, The above removing the encapsulant; (5) Formed during step (3) The array Carbon Nanostructures on the body depositing or forming a metal-based coating on the substrate; (6) Molten solder material The array Carbon Nanostructures On the body The infiltration process; (7) The solder-carbon nanostructure, in which the carbon nanostructure is dispersed within the composite. body To form a complex, the allowing the mixture to cool; and (8) Optionally, the solder-carbon nanostructure body and c) encapsulating the composite in a polymer or blend of polymers.
[0078] Solder-carbon nanostructures as described herein body In a method for forming a complex, a second exemplary method includes the steps of: (1) forming or providing a carbon nanostructure array; (2) optionally encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which may be a polymer-based material; (3) optionally exposing the optionally encapsulated carbon nanostructure array to a treatment that creates defect sites on the carbon nanostructures; (4) optionally removing the mounting medium; (5) Formed during step (3) The array Carbon Nanostructures on the body depositing or forming a metal-based coating on the substrate; (6) Molten solder material The array Carbon Nanostructures On the body a penetrating step, wherein the solder material remains in a liquid state; (7) Optionally, the solder-carbon nanostructure body and c) encapsulating the composite in a polymer or blend of polymers.
[0079] Solder-carbon nanostructures as described herein body In the method of forming a complex, a third exemplary method includes the steps of: (1) forming or providing a carbon nanostructure array; (2) encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which is a polymer-based material; (3) depositing or forming a metal-based coating on the encapsulated carbon nanostructures of the array; (4) infiltrating the encapsulated carbon nanostructures of the array with a molten solder material; (5) The solder-carbon nanostructure, in which the carbon nanostructure is dispersed within the composite. body To form a complex, the allowing the mixture to cool; and (6) Optionally, the solder-carbon nanostructure body and encapsulating the composite in a polymer or blend of polymers.
[0080] For the second method, the polymer encapsulant (particularly conjugated polymers) can act as a non-covalent functionalization mechanism for the carbon nanostructure (i.e., carbon nanotube) sidewalls. Aromatic molecules such as pyrene, porphyrin, polyacetylene, polythiophene, polyfluorene, polypyrrole, and poly(phenylenevinylene) and their derivatives on the polymer encapsulant can interact with the carbon nanotube sidewalls through π-π stacking and van der Waals interactions between the conjugated polymer chains containing aromatic rings and the surface of the carbon nanostructure (i.e., carbon nanotube) sidewalls. The polymers can have any suitable weight average molecular weight or polydispersity. In some examples, the weight average molecular weight can range from 2,000 Da to 750,000 Da and subranges disclosed therein. These polymers can wrap around the nanotubes and can act as functionalization sites through functional groups incorporated into the polymer itself, through nanoparticle dispersions incorporated into the polymer matrix, or by modifying the surface energy mismatch between the carbon nanostructure and a subsequent metal-based coating deposited thereon. Exemplary functional groups on the polymer include, for example, phosphines, phosphonates, phosphonic acids, diphosphenes, sulfonates, thiols, amines, amides, carboxylic acids, carboxylates, haloalkanes (C containing halogen substituents), 1 -C 10 Alkane, etc.), hydroxyl, ether, ester groups, or combinations thereof.
[0081] The final step of each of the above exemplary methods is to form a solder-carbon nanostructure. bodyThe composite is optionally encapsulated in a polymer or blend of polymers after formation of the composite, the encapsulant being typically a polymer-based coating formed from one or more polymers selected from, but not limited to, conjugated polymers, non-conjugated polymers, and / or aromatic polymers. In some examples, the polymer is a thermoplastic elastomer such as polyester-based polyurethane or styrene-ethylene-butylene-styrene, polyimide, polyamide, or blends thereof. The polymer-based encapsulant coating can be spray-coated onto the composite, or the composite can be immersed in a polymer solution. In some other embodiments, the polymer-based coating comprises one or more oligomeric materials, polymeric materials, or combinations thereof. In certain embodiments, the polymer may be selected from poly(3,4-3 ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS), poly(3,4-3 ethylenedioxythiophene) (PEDOT), polythiophene (including alkyl-substituted polythiophene), polystyrene, silicone, polysiloxane, polypyrrole, polyacetylene, polyaniline, polyfluorene, polyphenylene, polypyrene, polyazulene, polynaphthalene, polycarbazole, polyindole, polyazepine, poly(3,4-ethylenedioxythiophene), poly(p-phenylsulfide), and poly(p-phenylenevinylene), polyacetylene, polydiacetylene, and blends thereof. In certain cases, the polymer may be selected from silicone or polysiloxane. The polymer classes listed above include substituted polymers in which the polymer backbone is substituted with one or more functional groups, such as alkyl groups. The polymer can have any suitable weight average molecular weight or polydispersity. In some examples, the weight average molecular weight can range from 2,000 Da to 750,000 Da and subranges disclosed therein. It is believed that a secondary polymer coating can protect the exterior surface from exposure to the solder material in the composite where corrosion, embrittlement, diffusion, electrical insulation, handling, or other reliability or installation concerns are relevant.
[0082] A non-limiting representation of the first method above, excluding the optional use of an encapsulant, is shown in Figure 1. In certain embodiments, the methods described herein may be carried out in an inert, non-reactive environment to prevent undesired chemical reactions.
[0083] A. Carbon Nanostructure Arrays Exemplary methods for forming the carbon nanostructure (ie, carbon nanotube) arrays in step (1) of the method above are described in this section.
[0084] In certain embodiments, the carbon nanostructures are vertically aligned forests or arrays of tubular structures (i.e., carbon nanotubes). In certain embodiments, the vertically aligned carbon nanostructures are first order, second order, third order, or higher order multi-walled carbon nanotubes.
[0085] In some embodiments, the vertically aligned carbon nanotube array comprises: The metal is supported on or alternatively attached to a support or substrate formed at least in part from a metal, such as, but not limited to, aluminum, cobalt, chromium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, copper, or a combination thereof, and / or one or more metal oxides, such as the oxides of the metals listed above. In other embodiments, the support material can be, but is not limited to, ceramics and silicon or silicon compounds, such as silicon dioxide. In certain other embodiments, the substrate or support is a metal foil, such as, but not limited to, aluminum foil or copper foil.
[0086] The arrays can be formed by any suitable method known in the art for forming such arrays or forests on a substrate. In a preferred embodiment, the arrays are formed from vertically aligned carbon nanostructures on a support or substrate. Carbon nanostructures are said to be "vertically aligned" when they are substantially perpendicular to the surface on which they are supported or attached. Carbon nanotubes are said to be substantially vertical when they are oriented within an average of 30, 25, 20, 15, 10, or 5 degrees of the surface normal. Preferably, the nanotubes are spaced an optimal distance apart from one another and are of uniform height. In certain embodiments, the diameter of the carbon nanostructures ranges from 10 to 40 nm, more preferably 15 to 30 nm, and most preferably about 20 nm or less. The length of the carbon nanostructures (i.e., carbon nanotubes) forming the arrays can range from 0.01 to 5,000 microns, preferably 0.1 to 2500 microns, preferably 0.1 to 2000 microns, more preferably 0.1 to 1000 microns. In other embodiments, the carbon nanostructures form, but are not limited to, fibers, wires, horns, cones, or other tubular structures having high aspect ratios (i.e., greater than 1) with lengths as described above.
[0087] In a preferred embodiment, the carbon nanostructures (i.e., carbon nanotubes) are grown at a growth temperature below the melting temperature of the metal or metal alloy substrate or support. In a specific embodiment, the carbon nanostructures are grown at a growth temperature of about 600°C to about 660°C, more preferably about 610°C to about 650°C, and most preferably about 620°C to about 640°C.
[0088] Any suitable carbon source gas may be utilized. In some embodiments, the carbon source gas is acetylene. Other suitable carbon source gases include ethene, ethylene, methane, n-hexane, alcohols, xylene, metal catalyst gases (e.g., carbonyl iron), and combinations thereof.
[0089] In certain other embodiments, arrays of vertically aligned carbon nanostructures (i.e., carbon nanotubes) can be fabricated on another surface and transferred to a support or substrate made of a metal, metal alloy, ceramic, silicon-based, or other suitable material using methods known in the art.
[0090] In some embodiments, carbon nanotube arrays are formed on one or both sides of a substrate or support.
[0091] B. Metal-Based Coatings on Carbon Nanostructure Arrays In the described method, Array Carbon Nanostructures The body The carbon nanostructures may be coated with a metal-based coating, such as, but not limited to, a nanoscale coating formed from one or more layers of a metal, metal alloy, or metal oxide, which improves the wetting and / or dispersion of the carbon nanostructures within the solder material forming the composite.
[0092] However, prior to the deposition or formation of the metal coating in step (5) of the first or second method, Array Carbon Nanostructures To the bodyThe introduction of additional defects beyond those found in the as-formed array can be pursued. In some examples, the method can rely solely on defects formed during the carbon nanostructure growth process, and in such examples, step (3) of the first method above can be omitted (considered optional). Introducing additional defect sites into the carbon nanostructures beyond those found in the as-formed array can be accomplished in the first method described by the following steps: (2) encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant that is a polymer-based material; and (3) exposing the encapsulated carbon nanostructure array to a treatment that creates defect sites on the carbon nanostructures. For example, when the carbon nanostructures are carbon nanotubes, the carbon nanotubes can contain defects such as vacancies, interstitials, most commonly bond rotations and non-hexagonal rings (e.g., 5-C pentagonal defects). In some examples, the use of encapsulant polymers can also provide further functionalization of the carbon nanostructures. In such cases, the polymer encapsulant (especially conjugated polymers) can act as a non-covalent functionalization mechanism for the carbon nanostructure (i.e., carbon nanotube) sidewalls. Aromatic molecules such as pyrene, porphyrin, polyacetylene, polythiophene, polyfluorene, polypyrrole and poly(phenylenevinylene) and their derivatives on a polymer encapsulant can interact with the carbon nanotube sidewalls through π-π stacking and van der Waals interactions between the conjugated polymer chains containing aromatic rings and the surface of the carbon nanostructure (i.e., carbon nanotube) sidewall. The polymers can have any suitable weight average molecular weight or polydispersity. In some examples, the weight average molecular weight can range from 2,000 Da to 750,000 Da and subranges disclosed therein. These polymers can wrap around the nanotubes and can act as functionalization sites through functional groups incorporated into the polymer itself, through nanoparticle dispersions incorporated into the polymer matrix, or by modifying the surface energy mismatch between the carbon nanostructure and a subsequent metal-based coating deposited thereon.Exemplary functional groups on the polymer include, for example, phosphines, phosphonates, phosphonic acids, diphosphenes, sulfonates, thiols, amines, amides, carboxylic acids, carboxylates, haloalkanes (C containing halogen substituents). 1 -C 10 Alkane, etc.), hydroxyl, ether, ester groups, or combinations thereof.
[0093] Array Carbon Nanostructures On the body Treatment (i.e., plasma-based or acid bath) can be used to introduce additional defects to form an array of defect-containing carbon nanostructures (i.e., carbon nanotubes). In some examples, the carbon nanostructure array (i.e., carbon nanotubes) contains about 1%-50%, 1%-40%, 1%-30%, 1%-25%, 1%-20%, 1%-15%, 1%-10%, or 1%-5% more defects than the amount of defects in the as-formed and untreated carbon nanostructures (i.e., carbon nanotubes) of the array.
[0094] The carbon nanostructure array grown on the substrate has an optional encapsulant applied thereon in step (2) of the method to form a protective layer on the carbon nanostructure array (i.e., carbon nanotubes) and / or to provide functionalization thereon. The encapsulant is a polymer-based coating formed from one or more polymers selected from, but not limited to, conjugated polymers, non-conjugated polymers, and / or aromatic polymers. In some examples, the polymer is a thermoplastic elastomer such as a polyester-based polyurethane or styrene-ethylene-butylene-styrene, polyimide, polyamide, or blends thereof. In certain embodiments, the polymer may be selected from poly(3,4-3 ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS), poly(3,4-3 ethylenedioxythiophene) (PEDOT), polythiophene (including alkyl-substituted polythiophene), polystyrene, silicone, polysiloxane, polypyrrole, polyacetylene, polyaniline, polyfluorene, polyphenylene, polypyrene, polyazulene, polynaphthalene, polycarbazole, polyindole, polyazepine, poly(3,4-ethylenedioxythiophene), poly(p-phenylsulfide), and poly(p-phenylenevinylene), polyacetylene, polydiacetylene, and blends thereof. In certain cases, the polymer may be selected from silicone or polysiloxane. The polymer classes listed above include substituted polymers in which the polymer backbone is substituted with one or more functional groups, such as alkyl groups.
[0095] The encapsulant, a polymer-based coating, can be spray coated or the array of vertically aligned carbon nanostructures can be dipped into the polymer solution. The polymer solution for spray or dip coating can be prepared in a solvent suitable for the one or more polymers dissolved therein. The solvent can be an organic solvent such as tetrahydrofuran. The concentration of the polymer in the polymer solution can range from about 0.1 to 10% by weight or 0.1 to 5% by weight of the solvent. If necessary, heat and / or vacuum can be applied to control or facilitate removal of the solvent during the wet processing of step (2) of the method. In some other embodiments, the polymer-based coating comprises one or more oligomeric materials, polymeric materials, or combinations thereof. Following step (2), the carbon nanostructure array may be covered by a porous or semi-porous membrane or film of the polymer-based encapsulant. It is believed that the polymer-based encapsulant membrane / film protects the carbon nanostructures from deleterious effects from treatments such as plasma and acid treatments used in the first method. However, it is believed that the pores in the encapsulant allow these treatments to create defect sites on the carbon nanostructures through the sites exposed by the pores, while the non-porous portion of the membrane / film acts as a barrier to the treatments. Thus, the encapsulant can provide a protective barrier to the carbon nanostructure arrays (i.e., carbon nanotubes) when exposed to plasma and / or acid bath treatments by preventing destruction of the carbon nanostructures (i.e., carbon nanotubes), such as by oxidation, and / or delamination of the carbon nanostructures (i.e., carbon nanotubes) from the substrate on which they were grown.
[0096] During the optional encapsulation process of step (2), solvent evaporation can introduce capillary-induced agglomeration of the carbon nanotubes of the array. In the case of plasma treatment, as described below, this can allow for greater plasma penetration into the exposed carbon nanotube sidewalls.
[0097] Exemplary treatments that can be applied during step (3) of the first or second methods above to generate / induce the formation of defects on carbon nanostructures (i.e., carbon nanotubes) include, but are not limited to, plasma-based treatments (i.e., oxygen plasma) and / or acid bath treatments (i.e., nitric acid baths). Such treatments can result in improved defect formation compared to arrays that have not been treated with plasma and / or acid bath treatments. Array Carbon Nanostructures On the body Creating additional defect sites The introduction of defect sites enhances and improves the ability to deposit metals and mixtures thereof to form metal-based coatings.
[0098] In the case of plasma-based treatments, such as oxygen plasma, these can be applied by placing the array of optionally encapsulated carbon nanostructures in a suitable plasma processing device or chamber. Methods for performing oxygen plasma treatments and controlling their parameters are known in the art. In some examples, the power used during oxygen plasma treatment is in the range of about 1 to about 20 watts. The duration of exposure in step (3) can be for a time in the range of about 1 to about 60 seconds or about 1 to about 30 seconds.
[0099] In an acid bath treatment, such as a nitric acid bath, the optionally encapsulated carbon nanostructures of the array are exposed to acid by immersing the array in an acid-containing solution in a container. Array Carbon Nanostructures To the bodyDropwise addition of an acid-containing solution of 1000 ppm can be used. The acid, such as nitric acid, is diluted in a suitable solvent, such as ethanol, until a pH of about 1-2 is reached, and the solution is used as above. In some other instances, a higher pH is preferred, for example pH 5-6. It has been observed that a pH in the range of 1-2 may be more favorable for tip-based metal deposition in subsequent steps, while a higher pH (5-6) may result in more uniform deposition along the length of the carbon nanostructure (i.e., carbon nanotube). An exemplary reaction scheme (functionalization followed by metallization with Ag) is shown below. Coating is typically performed in 1-5 minutes. After deposition is complete, the solution may be evaporated and the coated substrate may be removed from the bath and washed with water or other suitable solvent to stop the reaction.
[0100] If present, the optional encapsulant (i.e., protective layer) may then be removed by dissolving in a solvent that will dissolve any encapsulant present or remaining after step (3). Array Carbon Nanostructures Body The exposure can be removed, if desired, during step (4) of the first or second methods above. In some instances, a treatment such as oxygen plasma can etch away the encapsulant (i.e., protective layer) during the exposure step (3), with the encapsulant (i.e., protective layer) acting as a sacrificial layer without requiring subsequent removal of any encapsulant.
[0101] Continue with step (3) of the first method Array Carbon Nanostructures body( Following the formation of additional defect sites on the carbon nanostructures (i.e., carbon nanotubes), a metal-based coating is applied to improve the wetting and dispersibility of the carbon nanostructures (i.e., carbon nanotubes) in the solder material. Generally, the metal-based coating can be applied using any technique known in the art.
[0102] Following encapsulation of the carbon nanostructure array (i.e., carbon nanotubes) following step (2) of the third method, a metal-based coating is applied to improve the wetting and dispersibility of the carbon nanostructures (i.e., carbon nanotubes) in the solder material. Generally, the metal-based coating can be applied using any technique known in the art.
[0103] As discussed above with respect to the first and second methods, the presence and / or introduction of defect sites allows for the easy deposition or formation of metal-based coatings on the carbon nanostructure arrays (i.e., carbon nanotubes). Additionally, the presence of an encapsulant polymer may also provide functional groups that allow for the easy deposition or formation of metal-based coatings when an encapsulant is present in either the first and / or second methods. The metal-based coating may be a coating such as, but not limited to, a nanoscale coating formed from a metal, a metal alloy, and / or a metal oxide. In some embodiments, the coating is made of one or more layers that may be made of one or more metal oxides such as, but not limited to, aluminum, bismuth, cobalt, chromium, zinc, gallium, tantalum, platinum, gold, nickel, iron, tin, lead, silver, tungsten, titanium, indium, copper, or combinations or alloys thereof, and / or oxides of the listed metals.
[0104] In some particular examples, the metal-based coating of the method is matched to a solder material composition, or Array Carbon Nanostructures Body The metal is selected to match at least one or more metals present in the solder material being dispersed. For example, most solders contain tin as a major component. Any suitable solder known in the art can be used. Thus, the metal-based coating can be applied to the solder-carbon nanostructure. bodyTo form a composite, it can be selected to include tin and optionally one or more additional metals that are commonly used in solder alloys to improve the wetting and dispersibility of the carbon nanostructures in a particular solder material.
[0105] In certain embodiments of the first or second methods, the carbon nanostructures (i.e., carbon nanotubes) are coated on the sidewalls of the CNTs and, optionally, on the tips of the carbon nanostructures (i.e., carbon nanotubes), or vice versa. In certain other embodiments, the carbon nanostructures (i.e., carbon nanotubes) are conformally coated on both the sidewalls of the carbon nanostructures (i.e., carbon nanotubes) and the tips of the carbon nanostructures (i.e., carbon nanotubes).
[0106] In some instances, capillary agglomeration can be induced within the carbon nanostructures by a process in which the carbon nanostructure array is first wetted with a suitable solvent capable of wetting the array, and then the solvent is dried prior to subsequent coating with metal according to the described methods. This more readily exposes the sidewalls of the array for subsequent metal coating. Array Carbon Nanostructures Body This is believed to allow for more effective penetration beyond the tip towards the base of the nanostructure.
[0107] In certain embodiments, at least about 100%, 99%, 98%, 97%, 96%, 95%, 90%, 80%, 70%, 60%, or 50% of the surface of the carbon nanostructure (i.e., carbon nanotube) is coated with the metal-based coating. In certain non-limiting embodiments, the thickness of the metal-based coating, such as the nanoscale conformal coating, can range from 0.1 to 1,000 nanometers, 1 to 500 nanometers, 5 to 250 nanometers, and more preferably from 5 to 100 nanometers, 5 to 50 nanometers, or 5 to 25 nanometers.
[0108] In the described method, the metal-based coating can include one or more coatings of metals, metal alloys, metal oxides, or combinations thereof that can be applied using atomic layer deposition (ALD). 1 of 1 One or more coatings can be deposited, in certain other examples, via chemical vapor deposition (CVD) or the like, on the plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming the array. In still other embodiments, a metal, metal alloy, metal oxide, or combination thereof can be deposited on the plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming the array. 1 of 1 One or more coatings can be deposited, such as by sputtering, onto a plurality of vertically aligned carbon nanostructures (ie, carbon nanotubes) forming an array.
[0109] Methods of ALD, CVD, and sputter coating metal-based coatings, as well as the reaction conditions and equipment required to achieve such metal-based coatings, are well known in the art. Selection of appropriate metal precursors to form the desired metal-based coating includes, but is not limited to, aluminum, bismuth, cobalt, chromium, zinc, gallium, tantalum, platinum, gold, nickel, iron, tin, lead, silver, tungsten, titanium, indium, copper, and alloys / combinations are also known.
[0110] For example, deposition techniques used to deposit one or more coatings on carbon nanostructures are generally deposited by CVD or ALD, etc., in which gas precursors containing the source material of the coating are fed into a closed chamber containing the enclosed array. The chamber can be at atmospheric pressure or various grades of vacuum. The chamber walls can be hot, or a heating stage can be used in conjunction with cold chamber walls to increase the deposition rate on the target object (i.e., the CNTs of the array). Methods for forming thin films by CVD are well known in the art. See, for example, SACampbell, Science and Engineering of Microelectronic Fabrication, 2003, Vol. 1, No. 1, pp. 1111-1115, 2003. nd Edition, Oxford University Press, New York (2001), which is incorporated herein by reference in its entirety. CVD deposition techniques for metals and metal oxides, such as aluminum oxide and silicon oxide, are known. In certain embodiments, the CVD deposition rate can be as low as 1 nm / cycle.
[0111] In a specific, non-limiting example, the surface of a plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming an array is coated by ALD with a platinum coating. The platinum coating may have any suitable thickness, but in some examples may be a 20 nm thick coating. For example, platinum is a low-reactivity metal that is believed to allow flux-free infiltration of the array with molten solder material, and thus the solder-carbon nanostructures. body There are also a wide variety of platinum precursors readily available for use in ALD processes. As mentioned previously, a general limitation of metal ALD is the availability of reducing agents that can adsorb and exothermically react with the surface-adsorbed metal precursors, allowing the ALD to proceed below 350 °C. Of all ALD metal deposition processes, ALD tungsten (W) is most commonly achieved using tungsten hexafluoride (WF 6 ) and silane (SiH 4 ) or disilane (Si2 H 6 ) as reactants.
[0112] In certain other non-limiting embodiments, the metal-based coating formed during step (5) of the first or second method or step (3) of the third method is alternatively formed by a wet coating method. In such a method, the surface of a plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming an array is infiltrated with a liquid phase containing a metal precursor capable of decomposing into elemental metal, thereby forming and depositing the metal on the surface of the carbon nanostructures (i.e., carbon nanotubes), particularly at defect sites that facilitate the formation / deposition of the metal from the precursor. The decomposition of the metal precursor and the formation of the metal-based coating therefrom is typically accomplished by immersing the array-forming carbon nanostructures (i.e., carbon nanotubes) in a suitable solvent containing the metal precursor dissolved therein and applying heat in an inert environment to pyrolyze the metal precursor and form the coating.
[0113] In the wet coating method, the metal precursor is dissolved in a suitable solvent and the solution is applied in step (3), for example by immersing the array in the solution. Array Carbon Nanostructures On the body Exemplary precursors include metal isopropoxides (e.g., copper(II) isopropoxide, vanadium(V) oxytriisopropoxide, titanium(IV) isopropoxide), metal hydrides (e.g., titanium hydride, AlH 3 {O(C 4 H 9 ) 2 , AlH 3 {N(CH 3 ) 3}), galistan (an alloy of tin, gallium and indium), and metal salts (such as, but not limited to, silver nitrate, silver neodecanoate, silver oxalate, silver acetate, silver tartrate, silver hexafluoroacetylacetonate cyclooctadiene, copper acetate, copper formate tetrahydrate, copper formate, copper glycolate, copper lactate, copper oleate and copper hydroxide) or palladium thiolate. Suitable solvents for dissolving the precursor include, for example, organic solvents such as alcohols (such as ethanol, methanol, isopropanol, etc.), xylene, glycols (such as ethylene glycol), glycol ethers, aromatic solvents, aliphatic solvents, toluene and acetone. Suitable mixtures of organic solvents are also possible. In some examples, the solution for dissolving the precursor may include water and an acid (such as formic acid). In some examples, the solution for dissolving the precursor may contain complexing agents and / or additives, such as, but not limited to, ethylamine, propylamine, butylamine, hexylamine, n-dimethyloctylamine, diamine, ammonium hydroxide, formic acid, ethanolamine, 2-hydroxyethyl-cellulose, ethylcellulose, or combinations thereof, as needed. The concentration of the metal precursor in the solvent may be any suitable concentration, such as, but not limited to, about 0.01-0.3 M, 0.01-0.2 M, or 0.01-0.1 M.
[0114] In some instances, Array Carbon Nanostructures on the body If an amorphous carbon cap is present, it may be necessary to perform an optional decapping step by boiling the array in an acetone bath for about 30 minutes before step (5) of the first or second method or step (3) of the third method if a wet coating method is used. The decapping step removes amorphous carbon from the array that may interfere with metal deposition during the wet coating method.
[0115] Once the solution is infiltrated, the array is heated to a temperature sufficient to decompose the precursors into their elemental metals. The defects on the carbon nanostructures provide sites for attachment of the metals deposited on the carbon nanostructures. Pyrolysis can be accomplished by placing the solution infiltrated array in a furnace or microwave or under a plasma and heating at a temperature of at least about 50°C, 75°C, 100°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, or 500°C. The pyrolysis temperature used to decompose the precursors may range from about 100°C to about 500°C and any subranges therein. Pyrolysis can also be accomplished by exposing the solution infiltrated array to a plasma, such as a hydrogen plasma, sufficient to decompose the metal precursors. The decomposition temperature can be reached by heating the array at a suitable ramp rate of about 1°C / min or 2°C / min until the final desired temperature is reached, followed by holding at that temperature for at least about 5-30 minutes, 5-25 minutes, 5-20 minutes, or 5-10 minutes. The pyrolysis process described is typically carried out under an inert atmosphere of nitrogen or argon. After a holding time sufficient to decompose the precursors and form a metal coating on the carbon nanostructures, the array may be cooled to room temperature (25°C) at a controlled cooling rate of about 1°C / min, 2°C / min, or 3°C / min, as appropriate, until cooled. In some other examples, the infiltrated array may be baked under an inert atmosphere (i.e., argon) for at least about 1, 2, 3, 4, or 5 hours to decompose the metal precursors to their elemental forms, thereby depositing the metals, particularly at defect sites on the carbon nanostructures that are the attachment points of the metals. In some examples, after pyrolysis, the metal-coated carbon nanostructures are dried for at least about 1-5 minutes and then plasma sintered.
[0116] In some other examples, instead of pyrolysis, as described above, the reduction of the metal precursor to elemental metal can be achieved by the use of photocuring, e.g., at low temperatures, and without the need for heating if necessary. In photocuring, the metal solution can be exposed to a high energy light source, e.g., UV light. The method of photocuring and the selection of its conditions, materials and parameters are known in the art. In some examples, when photocuring is used to form a metal coating on carbon nanostructures from a suitable metal precursor, the irradiance from the UV source induces the reduction of the metal precursor to elemental metal, Array Carbon Nanostructures on the body Optionally, about 0.1 W / cm for any suitable period of time necessary to form a metal coating on 2 ~100W / cm 2 In some examples, the irradiance may be applied for a period ranging from about 1 second to 1 hour.
[0117] In some example methods, for example when wet coating carbon nanostructures with galistan in acetone to form a metal coating, it can be important to control the pH of the solution to modify the wetting properties of the carbon nanostructures. For example, as discussed in the Examples, Array Carbon Nanostructures body( A pH of about 8 was required to allow wetting of the nanotubes (i.e., carbon nanotubes). The pH of the solution can be modified, if necessary, using an appropriate acid or base to improve the wetting properties.
[0118] In certain embodiments, after deposition / formation of the metal-based coating in step (5) of the first or second method or step (3) of the third method, an optional heat treatment can be applied to the surface of the plurality of vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming the array. For example, if the metal-based coating is a low melting point metal such as tin or a tin alloy, it can be beneficial to heat the coating above its melting temperature to further distribute the coating within the vertically aligned carbon nanostructures (i.e., carbon nanotubes) forming the array.
[0119] Following step (5) of the first or second method or step (3) of the third method, the array of metal-coated carbon nanostructures are infiltrated with a molten solder material during step (6) or step (4), respectively. The solder is a metal or metal alloy selected from, but not limited to, aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof. In some cases, the composite solder material is gold-tin solder, tin-silver-copper solder, tin-copper solder, tin-lead solder, tin-chromium solder, gallium solder, gallium-indium-tin solder, or indium solder. In some cases, the solder is a commercially available solder material known in the art, such as a lead-free solder. The solder is typically formed primarily of tin, optionally alloyed with other metals. The composition of the solder material can be selected to have any suitable melting temperature or melting temperature range from about -19 to 300°C. The melt can be formed by heating the solder to a suitable temperature to form a melt and introducing the array of metal coated carbon nanostructures therein. The solder material can be melted using any suitable heating means, such as an oven, in any suitable vessel for carrying out the infiltration step (6) of the first method or the infiltration step (4) of the second method.
[0120] Infiltration with molten solder during step (6) of the first or second method or infiltration step (4) of the third method can be carried out by several techniques. In one example, the prepared array (functionalized and conformal metal coated) can be dip coated into a molten solder bath for infiltration. Alternatively, the solder can be applied in either film or sheet form. Array Carbon Nanostructures Body It can be applied only to the tip, or it can be deposited in thin film form by sputtering or jet vapor deposition (JVD). Array Carbon Nanostructures On the body After applying a thin film of solder, the solder can be immersed or coated in solder flux in ambient air, vacuum, or in an inert (e.g., argon) environment, or reflowed to wet and penetrate the array in a formic acid or forming gas vapor environment if flux is not desired, under pressure, or any combination of the above.
[0121] In some examples, the infiltration of step (6) of the first or second method or infiltration step (4) of the third method is performed for a time ranging from about 0.1 to 200 minutes, about 15 to 150 minutes, or about 20 to 120 minutes. The leave time may be modified as needed depending on the selection of solder material. In some cases, during step (7) of the first method or infiltration step (5) of the third method, the infiltrated array can be controllably cooled to one or more selected temperatures at a suitable cooling rate ranging from about 0.1 to about 50 °C / min. The cooling time varies depending on the cooling rate. In some other embodiments, gas, liquid, or flash cooling / rapid quenching techniques known in the art can be applied. Gases such as nitrogen and argon can be used during cooling step (7) of the first method or infiltration step (5) of the third method. In some non-limiting embodiments, quenching the composite in a liquid mass to induce quenching can be applied as a cooling method. In certain embodiments, after the composite has cooled and hardened, the composite may be subjected to a further annealing process.
[0122] Optionally, mechanical mixing or stirring may be applied during step (6) of the first or second method or during the infiltration step (5) of the third method to improve the uniformity of the resulting solder-carbon nanostructure. body The uniformity of the carbon nanostructures dispersed throughout the composite can be controlled or improved, in some embodiments, the application of mechanical mixing or stirring can be used to reduce the time required to achieve uniform dispersion of the carbon nanostructures in the molten solder material.
[0123] In certain embodiments, the solder-carbon nanostructures described herein body The composites can be prepared by casting to form the composite as a sheet, plate, foil, rod, wire, strip, ingot, pellet, or chunk.
[0124] In certain other embodiments, the substrate or support may be formed from a material that is resistant to high temperatures and can be recovered and reused after being added to the molten solder. In some embodiments, a reusable substrate with an array formed on one or both sides can be immersed in a molten solder material in a controlled manner to release the carbon nanostructures (i.e., carbon nanotubes) from the substrate into the molten solder. Exemplary materials that can form a high temperature resistant substrate include, but are not limited to, titanium, tungsten, ceramics, and silicon-based materials. In some embodiments, after the molten solder has infiltrated and solidified the carbon nanostructure arrays (i.e., carbon nanotubes), the substrate or support is melted at a temperature higher than the temperature of the molten solder material to keep the substrate and the array of carbon nanotubes intact in their original orientation.
[0125] IV. Solder-Carbon Nanostructures body Use of the complex Solder-carbon nanostructures as described herein body The composites can be used in a variety of applications, including thermal applications.
[0126] In certain embodiments, the described solder-carbon nanostructures body The composite may be disposed or secured between a heat source and a heat sink or heat spreader, such as between an integrated circuit package and a heat exchanger, to improve the transfer of heat from the heat source to the heat sink or spreader.
[0127] In some embodiments, the solder-carbon nanostructure containing composites exhibit improved electrical conductivity, thermal conductivity, and mechanical properties compared to the initial solder that does not contain carbon nanostructures dispersed therein.
[0128] In certain embodiments, the solder carbon nanostructures including the composites described herein can be used as thermal interface materials (TIMs) in personal computers, server computers, memory modules, graphics chips, radar and radio frequency (RF) devices, disk drives, displays including light emitting diode (LED) displays, lighting systems, automotive control units, power electronics, solar cells, batteries, communication devices such as mobile phones, thermoelectric generators, and imaging devices including MRI.
[0129] In some examples, the device comprises a solder-carbon nanostructure body The composite may include a device that attaches a semiconductor die or chip to a substrate or package. In certain examples, the solder-carbon nanostructure including composite may be used to mount an electronic component, such as a semiconductor die or chip, to its substrate or package. For example, the solder-carbon nanostructure may include a composite that is capable of attaching a semiconductor die or chip to a substrate or package. body The composite attaches a semiconductor die or chip to a substrate or package. In some examples, the solder-carbon nanostructure containing composite may be involved in transporting heat and electricity through the layers as well as attaching the device in place. Additionally, in some examples, the conformal metal coating within the solder-carbon nanostructure containing composite provides radiation shielding properties that protect the underlying device from environmental radiation.
[0130] Solder-Carbon Nanostructures body The composites can be used to bond and experience less loss in die shear strength or thermal performance after exposure to thermal cycling (i.e., repeated thermal cycling) than similar solder-only joints (i.e., joints including only solder) exposed to the same number of cycles and fatigue failure mechanisms (i.e., high temperatures). Joints bonded with only solder or sintered silver and subjected to thermal cycling or high temperatures that experience fatigue failure are characterized by the presence of solder carbon nanostructures as described herein. body The composite is used to maintain mechanical and thermal contact when bonded. EXAMPLES
[0131] Example 1: Solder-Carbon Nanotube Composite Preparation of vertically aligned carbon nanotube arrays on aluminum substrates Argon, hydrogen, and CH as carbon source gases 2 H 2 Vertically aligned forests of carbon nanotubes (CNTs) were grown on one or both sides of 50 μm thick Al foils using a low pressure chemical vapor deposition process at 635 °C and 440 mbar in a tube furnace connected to a mass flow controller supplying 1000 μm of CNTs. Growth times were varied from 30 min to grow forests of multi-walled CNTs ranging in height from 15 μm with an average CNT diameter of 15 nm.
[0132] Coating vertically aligned carbon nanotube arrays with encapsulant To increase the availability of deposition sites on the carbon nanotube sidewalls, functionalization in the form of introducing strategic defects as sites for metal deposition was pursued. To prevent the problem of fracture of the carbon nanotubes in the array a, an encapsulant made of a thin polyester-based polyurethane (TPU) coating was used to protect the carbon nanotubes in the formed array.
[0133] The TPU coating was applied by wet processing using 3.0 wt% TPU polymer in tetrahydrofuran. Solvent evaporation from this process introduced capillary-induced agglomeration of the carbon nanotube arrays. In the case of oxygen plasma treatment described below, this allowed for greater plasma penetration into the exposed CNT sidewalls. The resulting coating resulted in a semi-porous film covering the carbon nanotubes of the array.
[0134] Introducing defect sites onto encapsulated vertically aligned carbon nanotube arrays After encapsulation with TPU, the arrays were subjected to either an acid bath treatment with nitric acid or an oxygen plasma treatment to introduce more defect sites into the carbon nanotube walls.
[0135] Acid bath treatment In one example, a dropwise addition of concentrated (97%) nitric acid was performed to form a solution of pH 5.8 in ethanol. The arrays were exposed to the solution. Nitric acid created defect sites on the carbon nanotube sidewalls at very low nitric acid concentrations. However, nitric acid also had a detrimental effect on carbon nanotube-substrate adhesion, as it attacked the iron catalyst that acts as a base anchor for the carbon nanotubes to the substrate. This resulted in delamination of the arrays into the nitric acid solution for carbon nanotube arrays that were not encapsulated by TPU.
[0136] O 2 Plasma treatment To maintain the adhesion of the CNT array to the substrate while introducing defect sites, 2 Plasma functionalization was also investigated. The plasma was 20 sccm O at 100 mTorr. 2 The grown CNTs were grown in a 13.56 MHz RF induction system using a 10 W 1300 MHz RF induction system. The CNTs were grown in a 10 W 1300 MHz RF induction system using a 10 W 1300 MHz RF induction system. The grown ... 2 The arrays were prone to destruction by oxidation from the plasma. An effort to protect the arrays from destruction during plasma functionalization can be accomplished by applying an encapsulant to the carbon nanotubes as described above.
[0137] The pores in the semi-porous TPU membrane allow for the release of O in the areas where the pores of the polymer coating are located without excessively disrupting the bulk carbon nanotube arrays. 2 This makes it possible to process. 2 During the plasma treatment, the TPU coating acted as a sacrificial layer that was etched away instead of the carbon nanotubes being destroyed. The polymer-agglomerated carbon nanotubes formed stronger and longer O 2 It was able to withstand plasma treatment.
[0138] Platinum deposition on arrays of carbon nanotubes after defect introduction by atomic layer deposition (ALD) Atomic layer deposition (ALD) was used to deposit metals onto plasma-treated carbon nanotube arrays protected by a TPU encapsulant. Three metal coatings were demonstrated: platinum, tungsten, and tungsten with an alumina cap. Platinum was selected as the deposition material due to its low reactivity, which allows flux-free infiltration of the arrays by liquid metals such as tin, good thermal conductivity, and the relative availability of platinum precursors for ALD deposition. The ALD process allowed the deposition of a 20 nm platinum coating onto the arrayed carbon nanotubes. Tungsten was selected due to its thermodynamically favorable low temperature process. An alumina cap was evaluated as a means to reduce the more difficult to remove passivation state common to pure tungsten.
[0139] Energy dispersive X-ray spectroscopy (EDX) confirmed the presence of platinum from the tip to the base of the array. However, after coating, the diameter of the tubes, measured in the region near the tip, was on the order of 25-45 nm along the z-axis of the array. However, measuring the diameter of the tubes from a top view of the array showed that the features on the top surface (tip) of the array were 45-60 nm thick. This suggested that platinum was preferentially deposited at the tips compared to the sidewalls of the nanostructures.
[0140] Further indicative of the coating gradient from tip to base was the observed tendency of the arrays to collapse into a narrower structure at the base. Typically, after exposing an encapsulated array to a fluid and then evaporating, the reverse was observed (collapse / clumping at the tip while the base remained stationary). Capillary action and volume expansion of the fluid associated with the evaporation process are known to exert forces on adjacent tubes, pulling them together in channels adjacent to the fluid escape path. The collapse at the base but not the tip suggested that the platinum coating effectively froze the array near the tip, forming a semi-continuous coating that could no longer allow individual nanotubes to slide independently of each other.
[0141] Further evidence that the platinum coating froze the carbon nanotube tips in place, in addition to agglomerating the base of the array, comes from thermal measurements of the coated arrays. Given that the platinum coating has a thermal conductivity of about 70 W / mK (based on the properties of elemental platinum), the effective thermal conductivity is expected to increase beyond the 12 W / mK of the uncoated array. However, when measured according to ASTM D5470 in a 1D steady-state system, the measured thermal resistance of the platinum-coated array was >4x that of the uncoated array. This strongly suggested that the platinum coating reduced the ability of the nanostructures to conform to the surface of the measurement bar, resulting in a reduced contact area and higher thermal resistance. It is expected that by reducing the coating thickness, the tendency of the platinum coating to overly stiffen the arrays can be minimized.
[0142] Deposition of metal coatings on arrays of carbon nanotubes after introduction of defects by a wet coating method A wet coating method (liquid phase infiltration method) was used to form metal coatings on the carbon nanotube arrays. This method proceeded by decomposition of metal precursors dissolved in a solvent, where the native metals were attached to the carbon nanotube arrays after decomposition, preferably bonding to defect sites on the carbon nanotube arrays. Metal precursors included silver nitrate, metal isopropoxides, metal hydrides, or galinstan.
[0143] Several metal solutions were investigated to produce well-dispersed metal coatings inside the carbon nanotube arrays as follows. [Table 2]
[0144] Metal Isopropoxides Three metal isopropoxides were investigated to determine their ability to penetrate and coat the interior of the CNT arrays: copper (Cu)(II) isopropoxide, vanadium (V) oxytriisopropoxide, and titanium (Ti)(IV) isopropoxide. For each material, the metal isopropoxide was dissolved in absolute ethanol, and then the carbon nanotube arrays were immersed in the solution and placed in a furnace. The metal isopropoxides were expected to pyrolyze to their base metals upon exposure to high temperatures in an inert environment, releasing -OH groups in the gas phase into the furnace exhaust. Each sample was heated to 450 °C at 2 °C / min for 10 min and cooled to 25 °C at 3 °C / min in a nitrogen atmosphere. After removal from the furnace, each sample was inspected using a digital microscope to determine the morphology of the resulting coating. The electrical resistance of each sample was also measured using a multimeter to confirm that a conductive (metallic) coating had been deposited on the arrays.
[0145] For all metal isopropoxide samples, the native carbon nanotube arrays were significantly destroyed, with large macroscopic spots present where the carbon nanotubes had been completely removed. Furthermore, the metal deposits tended to aggregate into large agglomerates that were not suitable for further processing.
[0146] Samples with Cu and Ti deposits showed moderate conductivity after coating (5-6 ohms at 1 inch probe spacing in the plane) and with sufficient roughness and contact resistance to exhibit approximately 5x the resistance of the native array (approximately 1 ohm at the same probe spacing) although the base metal was present.
[0147] The vanadium sample showed significantly higher resistance (approximately 30 ohms) than the Cu and Ti deposits. This may be due to the observed differences in the coating behavior of Va compared to the other metals. The Va deposit was mostly present on the foil substrate where the CNTs had been removed, with very little metal deposit on the CNTs themselves. On the other hand, both Cu and Ti showed deposits on the CNT array itself.
[0148] Titanium Hydride TiH in anhydrous ethanol solution 4 Powders were prepared and processed in the same manner as the metal isopropoxides described above. These samples provided a much more uniform Ti coating than either of the metal deposits derived from the metal isopropoxide solutions. For these samples, the resistance was measured first at the tip of the carbon nanotube array using optical pressure from a multimeter probe, then again deeper into the array using a larger contact force to create a penetration in the carbon nanotube / Ti composite for measurement. The resistance of this sample showed no discernible difference between the top of the array and the deeper layers of the array at 3.2 ohms. This suggests that the distribution of the Ti deposits was indeed relatively uniform and that the additional resistance over the native array was due to features that were uniformly present throughout the Ti carbon nanotube composite. This suggests that metal hydride decomposition may be an effective means of placing conductive deposits inside densely packed carbon nanotube arrays, but the increased electrical resistance suggests that a different base metal or improved processing methods may be necessary to create a composite with improved properties.
[0149] Galinstan Galinstan is a metallic alloy, a liquid metal alloy at room temperature. It is an alloy of tin, gallium and indium. As a proof of principle, a solution of Galinstan dispersed in acetone was prepared in an ultrasonic bath. At pH 6, the metal was found to be curled up at the top of the carbon nanotubes. Changing the pH of the solution, at pH 8.17, the tips of the carbon nanotubes appeared wet when viewed under magnification, although it was not clear whether Galinstan had penetrated the array.
[0150] silver nitrate In modifying the surface energy of vertically aligned carbon nanotube (CNT) arrays to improve their liquid metal solder wettability, silver has been investigated due to its inherently high thermal conductivity, chemical stability, and high wettability to solder. However, amorphous carbon is usually deposited inside the carbon nanotube arrays after the growth process to improve the overall structural dynamics of the arrays on their aluminum substrates. However, this carbon cap was found to hinder Ag nucleation. As a result, AgNO 3 The first step in the deposition was a decapping process in a boiling acetone bath for 30 min.
[0151] Silver was grown on the decapped carbon nanotube arrays from nucleation of a 0.1 M silver nitrate precursor in boiling ethanol solution for 10 min. Following silver nitrate deposition, the carbon nanotube arrays were calcined at 450 °C in argon for 3 h to completely decompose the silver nitrate to elemental silver.
[0152] Polymer (TPU) coated and uncoated arrays were treated with oxygen plasma for 30 seconds at 10 or 20 W up to 240 seconds, as shown in Table 1 below. The polymer agglomerated carbon nanotubes were able to withstand more powerful and longer plasma treatments, increasing the weight ratio of silver to carbon on the carbon nanotubes, as evidenced by Energy Dispersive Spectroscopy (EDS) analysis, to the point where the carbon nanotube coverage on the substrate began to decrease, as shown in Table 1 below. The optimized plasma parameters were 20 W power and 120 seconds. A plasma power of 30 W was also investigated, but significant carbon nanotube destruction was observed at this power, even at 30 seconds of treatment.
[0153] [Table 1]
[0154] Deposition of metal coatings on arrays of carbon nanotubes after introduction of defects by sputter coating method Finally, sputter coating of the arrays with a metal or metal layer to improve wetting of the arrays by a second metal or alloy, such as solder, was investigated. An example of a sputter coating consisted of a Ti-Ni-Au trilayer. 60 / 150 / 250 nm of Ti / Ni / Au was sputtered onto carbon nanotube arrays treated with all variations of the above techniques. Ti was chosen because it offers the possibility of direct bonding (through the formation of TiC) to the CNT sidewalls themselves and to the Ag deposits.
[0155] Infiltration of arrays of metal-coated carbon nanotubes with solder materials Finally, Sn-Ag-Cu solder was infiltrated into the metal-coated carbon nanotubes of the array by several techniques. The prepared arrays (functionalized and conformal metal coated) were dip-coated into a molten solder bath for infiltration. Alternatively, AuSn solder was applied to the tips of the array, either in film or sheet form, or deposited in the form of a thin film by sputtering or jet vapor deposition (JVD). After application of the thin film of solder to the array, it can be reflowed to wet and infiltrate the array.
[0156] Example 2: Solder-carbon nanotube composites formed using metal-organic decomposition (MOD) ink and their thermal performance evaluation Preparation of solder-carbon nanotube composites Metal-organic decomposition (MOD) inks can be used to reduce the decomposition temperature of the metal precursor source. For example, silver neodecanoate can be used as the silver source.
[0157] Silver neodecanoate was dissolved in a suitable organic solvent, xylene, at concentrations ranging from 5 to 40% by weight. The mixture was continuously stirred to aid dissolution.
[0158] This solution was applied to as-grown carbon nanotube (CNT) arrays without further functionalization using a pipette. In this example, it is believed that the defect sites generated during the CNT growth process can act as nucleation and anchoring points for the metal coating formed during decomposition.
[0159] A silver neodecanoate solution was applied to the arrays, which were then heated to high temperatures (150°C-250°C) in an oven. Different samples were baked at 200°C for 30 minutes. Examination of the thickness of the arrays after metallization showed the formation of a metallic silver coating with a thickness of around 1-50 micrometers.
[0160] The adhesion of the silver coating to the array was evaluated by sonication in a solvent (IPA / acetone). It was observed that the silver-encapsulated areas remained attached to the substrate even after the uncoated areas of the array peeled off. After coating with silver, Galinstan (an alloy of tin, gallium and indium) was infiltrated into the array by applying a drop and then spreading the material over the sample using a rotational motion or by spreading the material using a pipette.
[0161] Thermal performance evaluation To evaluate thermal performance, preforms of solder-carbon composites were prepared while still anchored to the aluminum substrate on which the carbon nanostructures were grown. The preforms were nominally about 500 μm thick and infiltrated with a gallium indium tin alloy. They were then cut to the size of TO-220 resistors, the resistors were attached to copper heat sinks using spring clips, and the solder-carbon nanostructures were then bonded to the aluminum substrate. body The composite served as a thermal interface material (TIM).
[0162] The performance of the solder-carbon nanotube composite was compared to a 90 μm thick carbon nanotube wax composite, which is known to provide excellent heat transfer properties. To control for thickness effects, a 500 μm thick carbon nanotube polymer composite was also compared to the solder-carbon nanotube composite.
[0163] It was observed that the 500 μm thick solder-carbon nanotube composite provided lower thermal resistance than the much thinner 90 μm carbon nanotube wax composite. It was also observed that a secondary polymer coating (wax) could be applied to the 500 μm solder composite and still maintain thermal performance comparable to the much thinner 90 μm thick carbon nanotube wax composite.
[0164] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the disclosed invention belongs. Publications cited herein and the materials for which they are cited are specifically incorporated by reference.
[0165] Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments of the invention described herein which equivalents are intended to be encompassed by the following claims. In certain embodiments, for example, the following are provided: (Item 1) A plurality of carbon nanostructures dispersed within a solder material, the plurality of carbon nanostructures including a metal coating thereon and having a length in the range of 1 to 1000 microns. A solder-carbon nanostructure composite comprising: the plurality of carbon nanostructures includes defects thereon due to exposure to plasma treatment, acid bath treatment, and / or due to a growth process of the plurality of carbon nanostructures; and / or the plurality of carbon nanostructures includes functional groups thereon due to a polymer encapsulating the plurality of carbon nanostructures; Solder-carbon nanostructure composites. (Item 2) 2. The solder-carbon nanostructure composite of item 1, wherein the carbon nanostructure is a carbon nanotube. (Item 3) 3. The solder-carbon nanostructure composite according to any one of items 1 to 2, wherein the functional group of the polymer encapsulating the plurality of carbon nanostructures includes a phosphine, a phosphonate, a phosphonic acid, a diphosphene, a sulfonate, a thiol, an amine, an amide, a carboxylic acid, a carboxylate, a haloalkane, a hydroxyl, an ether, an ester group, or a combination thereof. (Item 4) 4. The solder-carbon nanostructure composite according to any one of claims 1 to 3, wherein the polymer coating comprises or consists of a polymer material selected from a non-conjugated polymer, a conjugated polymer, or an aromatic polymer. (Item 5) 4. The solder-carbon nanostructure composite of any one of claims 1 to 3, wherein the polymer coating comprises or is formed from a thermoplastic elastomer selected from the group consisting of polyester-based polyurethane, styrene-ethylene-butylene-styrene, polyimide, polyamide, silicone, polysiloxane, and blends thereof. (Item 6) 6. The solder-carbon nanostructure composite of any one of claims 1 to 5, wherein the metal coating comprises one or more layers of a metal, a metal alloy, or a metal oxide, which enhances the wettability and dispersibility of the carbon nanostructures in the solder material. (Item 7) 7. The solder-carbon nanostructure composite of any one of items 1 to 6, wherein the metal coating comprises one or more layers of a metal selected from aluminum, cobalt, chromium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, copper, alloys thereof, metal oxides, and combinations thereof, which enhances wettability and dispersibility of the carbon nanostructures in the solder material. (Item 8) The solder-carbon nanostructure composite according to any one of items 1 to 7, wherein the solder material comprises a metal selected from the group consisting of aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof. (Item 9) The solder material is selected from the group consisting of gold-tin solder, tin-silver-copper solder, tin-copper solder, tin-lead solder, tin-chromium solder, gallium solder, gallium-indium-tin solder, and indium solder. The solder-carbon nanostructure composite according to any one of claims 1 to 7. (Item 10) 10. The solder-carbon nanostructure composite of any one of claims 1 to 9, wherein the plurality of carbon nanostructures dispersed within the solder material have controlled alignment along an in-plane direction, a cross-plane direction, or a mid-plane direction. (Item 11) the solder-carbon nanostructure composite has an electrical conductivity that is at least about 105%, 110%, 115%, 120%, 125%, 130%, 135%, 140%, 145%, 150%, or greater than the electrical conductivity of the initial solder material without any dispersed carbon nanostructures therein; and / or 11. The solder-carbon nanostructure composite of any one of claims 1 to 10, wherein the composite has a thermal conductivity that is at least about 20, 30, 50, or 70% greater than the thermal conductivity of the initial solder material without any dispersed carbon nanostructures therein. (Item 12) The complex has a diameter of about 5, 4, 3, 2, 1, 1.5, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.05, or 0.01 cm 2 and / or has a thermal resistance of less than K / W 12. The solder-carbon nanostructure composite according to any one of items 1 to 11, wherein the composite has a thermal conductivity in the range of about 1 to 2500 W / m·K, 1 to 2000 W / m·K, 1 to 1500 W / m·K, 1 to 1000 W / m·K, 1 to 500 W / m·K, 5 to 500 W / m·K, 5 to 400 W / m·K, 5 to 300 W / m·K, 5 to 200 W / m·K, 5 to 150 W / m·K, or 5 to 100 W / m·K. (Item 13) the composite is a thermal interface material, and the thermal interface material is about 5, 4, 3, 2, 1, 1.5, 1.0, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, 0.05, or 0.01 cm 2 13. The solder-carbon nanostructure composite according to any one of items 1 to 12, having a thermal resistance of less than K / W. (Item 14) 1. A method for producing a solder-carbon nanostructure composite, the method comprising: (1) forming or providing a carbon nanostructure array; (2) optionally encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which may be a polymer-based material; (3) optionally exposing the optionally encapsulated carbon nanostructure array to a treatment that creates defect sites on the carbon nanostructures; (4) optionally removing the encapsulant; (5) depositing or forming a metal-based coating on the array of carbon nanostructures formed during step (1); (6) infiltrating the carbon nanostructures of the array with molten solder material; (7) cooling the mixture to form the solder-carbon nanostructure composite having the carbon nanostructures dispersed within the composite; (8) optionally encapsulating the solder-carbon nanostructure composite in a polymer. (Item 15) Item 15. The method of item 14, wherein the carbon nanostructure array is a carbon nanotube array. (Item 16) 16. The method according to claim 14, wherein the polymer-based material is or comprises a polymeric material selected from a non-conjugated polymer, a conjugated polymer, or an aromatic polymer. (Item 17) 15. The method of claim 14, wherein the polymer-based material is a coating comprising or formed from polyester-based polyurethane, styrene-ethylene-butylene-styrene, polyimide, polyamide, silicone, polysiloxane, and blends thereof. (Item 18) 18. The method of any one of items 14 to 17, wherein the metal coating comprises one or more layers of a metal, a metal alloy, or a metal oxide, which enhances the wettability and dispersibility of the carbon nanostructures in the molten solder material. (Item 19) 18. The method of any one of items 14 to 17, wherein the metal-based coating comprises one or more layers of metals selected from aluminum, cobalt, chromium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, copper, alloys thereof, metal oxides, and combinations thereof, which enhances the wettability and dispersibility of the carbon nanostructures in the molten solder material. (Item 20) 20. The method according to any one of items 14 to 19, wherein the solder material comprises a metal selected from the group consisting of aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof. (Item 21) 20. The method according to any one of items 14 to 19, wherein the solder material is a gold-tin solder, a tin-silver-copper solder, a tin-copper solder, a tin-lead solder, a tin-chromium solder, a gallium solder, a gallium-indium-tin solder or an indium solder. (Item 22) 22. The method according to any one of items 14 to 21, wherein the treatment in step (3) is a plasma-based treatment or an acid bath treatment. (Item 23) 23. The method of any one of items 14 to 22, wherein the metal-based coating comprises one or more coatings formed from a metal, a metal alloy, and / or a metal oxide. (Item 24) 23. The method according to any one of items 14 to 22, wherein the metal base comprises one or more coatings made of one or more metal oxides, such as aluminum, bismuth, cobalt, chromium, zinc, gallium, tantalum, platinum, gold, nickel, iron, tin, lead, silver, tungsten, titanium, indium, copper, or combinations or alloys thereof, and / or oxides of the listed metals. (Item 25) 23. The method according to any one of claims 14 to 22, wherein the metal-based coating is selected to match the composition of the solder material or to match at least one or more metals present in the composition of the solder material. (Item 26) 26. The method according to any one of items 14 to 25, wherein the metal-based coating has a thickness in the range of about 0.1 to 50,000 nanometers, 500 to 50,000 nanometers, 1 to 10,000 nanometers, 5 to 5,000 nanometers, 5 to 1,000 nanometers, 5 to 500 nanometers, 5 to 250 nanometers, 0.1 to 1,000 nanometers, 1 to 500 nanometers, 5 to 250 nanometers, 5 to 100 nanometers, 5 to 50 nanometers, or 5 to 25 nanometers. (Item 27) 27. The method according to any one of items 14 to 26, wherein the metal-based coating is formed by atomic layer deposition, chemical vapor deposition, or sputter coating the metal-based coating. (Item 28) 27. The method according to any one of items 14 to 26, wherein the metal-based coating is formed by a wet coating method. (Item 29) 29. The method of claim 28, wherein the carbon nanostructures are infiltrated with a liquid phase containing a metal precursor that is thermally or photonically decomposed to form and deposit elemental metal on the surface of the carbon nanostructures. (Item 30) 30. The method of claim 29, wherein the metal precursor is selected from the group consisting of metal isopropoxides, metal hydrides, galistans, and metal salts. (Item 31) 30. The method of claim 29, wherein the metal isopropoxide is selected from the group consisting of copper(II) isopropoxide, vanadium(V) oxytriisopropoxide, and titanium(IV) isopropoxide. (Item 32) 30. The method of claim 29, wherein the metal salt is selected from the group consisting of silver nitrate, silver neodecanoate, silver oxalate, silver acetate, silver tartrate, silver hexafluoroacetylacetonate cyclooctadiene, copper acetate, copper formate tetrahydrate, copper formate, copper glycolate, copper lactate, copper oleate, copper hydroxide, nickel sulfate, and nickel acetate. (Item 33) 33. The method of any one of items 29 to 32, wherein the metal precursor is decomposed by placing the infiltrated array in a furnace and heating at a temperature of at least about 50°C, 75°C, 100°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, or 500°C, optionally under an inert atmosphere of nitrogen or argon. (Item 34) 34. The method according to any one of items 14 to 33, wherein the solder material is selected from the group consisting of aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof. (Item 35) 34. The method according to any one of items 14 to 33, wherein the solder material is selected from the group consisting of gold-tin solder, tin-silver-copper solder, tin-copper solder, tin-lead solder, tin-chromium solder, gallium solder, gallium-indium-tin solder or indium solder.
Claims
1. A plurality of carbon nanostructures dispersed within a solder material, the plurality of carbon nanostructures including a metal coating thereon and having lengths in the range of 1 to 1000 microns. A solder-carbon nanostructure composite comprising: the plurality of carbon nanostructures includes defects thereon due to exposure to plasma treatment, acid bath treatment, and / or due to a growth process of the plurality of carbon nanostructures; and / or the plurality of carbon nanostructures includes functional groups thereon due to a polymer encapsulating the plurality of carbon nanostructures; Solder-carbon nanostructure composite.
2. 2. The solder-carbon nanostructure composite of claim 1, wherein the carbon nanostructure is a carbon nanotube.
3. 3. The solder-carbon nanostructure composite of claim 1, wherein the functional groups of the polymer encapsulating the plurality of carbon nanostructures include phosphine, phosphonate, phosphonic acid, diphosphene, sulfonate, thiol, amine, amide, carboxylic acid, carboxylate, haloalkane, hydroxyl, ether, ester groups, or combinations thereof.
4. The solder-carbon nanostructure composite of any one of claims 1 to 3, wherein the polymer coating comprises or consists of a polymeric material selected from a non-conjugated polymer, a conjugated polymer, or an aromatic polymer.
5. 4. The solder-carbon nanostructure composite of claim 1, wherein the polymer coating comprises or is formed from a thermoplastic elastomer selected from the group consisting of polyester-based polyurethanes, styrene-ethylene-butylene-styrene, polyimides, polyamides, silicones, polysiloxanes, and blends thereof.
6. the metal coating comprises one or more layers of a metal, a metal alloy, or a metal oxide, which enhances the wettability and dispersibility of the carbon nanostructures in the solder material; or 6. The solder-carbon nanostructure composite of claim 1, wherein the metal coating comprises one or more layers of a metal selected from aluminum, cobalt, chromium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, copper, alloys thereof, metal oxides, and combinations thereof, which enhances the wettability and dispersibility of the carbon nanostructures in the solder material.
7. the solder material comprises a metal selected from the group consisting of aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof; or The solder-carbon nanostructure composite according to any one of claims 1 to 6, wherein the solder material is selected from the group consisting of gold-tin solder, tin-silver-copper solder, tin-copper solder, tin-lead solder, tin-chromium solder, gallium solder, gallium-indium-tin solder, and indium solder.
8. 8. The solder-carbon nanostructure composite of claim 1, wherein the plurality of carbon nanostructures dispersed within the solder material have controlled alignment along an in-plane direction, a cross-plane direction, or a mid-plane direction.
9. 1. A method for producing a solder-carbon nanostructure composite, the method comprising: (1) forming or providing a carbon nanostructure array; (2) optionally encapsulating the carbon nanostructures of the carbon nanostructure array in a suitable encapsulant, which may be a polymer-based material; (3) optionally exposing the optionally encapsulated carbon nanostructure array to a treatment that creates defect sites on the carbon nanostructures; (4) optionally removing the encapsulant; (5) depositing or forming a metal-based coating on the array of carbon nanostructures formed during step (1); (6) infiltrating the carbon nanostructures of the array with molten solder material; (7) cooling the mixture to form the solder-carbon nanostructure composite, the carbon nanostructures being dispersed within the composite; and (8) optionally encapsulating the solder-carbon nanostructure composite in a polymer.
10. The method of claim 9 , wherein the carbon nanostructure array is a carbon nanotube array.
11. The method according to any one of claims 9 to 10, wherein the polymer-based material is or comprises a polymeric material selected from a non-conjugated polymer, a conjugated polymer, or an aromatic polymer.
12. 10. The method of claim 9, wherein the polymer-based material is a coating comprising or formed from polyester-based polyurethane, styrene-ethylene-butylene-styrene, polyimide, polyamide, silicone, polysiloxane, and blends thereof.
13. the metal-based coating comprises one or more layers of a metal, metal alloy, or metal oxide, which enhances the wetting and dispersibility of the carbon nanostructures in the molten solder material; or 13. The method of any one of claims 9 to 12, wherein the metal-based coating comprises one or more layers of metals selected from aluminum, cobalt, chromium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, copper, alloys thereof, metal oxides, and combinations thereof, which enhances the wettability and dispersibility of the carbon nanostructures in the molten solder material.
14. the solder material comprises a metal selected from the group consisting of aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof; or 14. The method according to any one of claims 9 to 13, wherein the solder material is a gold-tin solder, a tin-silver-copper solder, a tin-copper solder, a tin-lead solder, a tin-chromium solder, a gallium solder, a gallium-indium-tin solder or an indium solder.
15. the metal-based coating comprises one or more coatings formed from a metal, a metal alloy, and / or a metal oxide; or 15. The method of any one of claims 9 to 14, wherein the metal-based coating comprises one or more coatings made of one or more metal oxides, such as aluminum, bismuth, cobalt, chromium, zinc, gallium, tantalum, platinum, gold, nickel, iron, tin, lead, silver, tungsten, titanium, indium, copper, or combinations or alloys thereof, and / or oxides of the listed metals.
16. the solder material is selected from the group consisting of aluminum, bismuth, copper, cobalt, chromium, gallium, zinc, tantalum, platinum, gold, nickel, iron, tin, lead, silver, titanium, indium, and alloys thereof; or 16. The method of any one of claims 9 to 15, wherein the solder material is selected from the group consisting of gold-tin solder, tin-silver-copper solder, tin-copper solder, tin-lead solder, tin-chromium solder, gallium solder, gallium-indium-tin solder or indium solder.
